Commutativity in the algorithmic Lovász local lemma - Kolmogorov, Vladimir (SIAM Journal on Computing)
We consider the recent formulation of the algorithmic Lov ́asz Local Lemma [N. Har-vey and J. Vondr ́ak, inProceedings of FOCS, 2015, pp. 1327–1345; D. Achlioptas and F. Iliopoulos,inProceedings of SODA, 2016, pp. 2024–2038; D. Achlioptas, F. Iliopoulos, and V. Kolmogorov,ALocal Lemma for Focused Stochastic Algorithms, arXiv preprint, 2018] for finding objects that avoid“bad features,” or “flaws.” It extends the Moser–Tardos resampling algorithm [R. A. Moser andG. Tardos,J. ACM, 57 (2010), 11] to more general discrete spaces. At each step the method picks aflaw present in the current state and goes to a new state according to some prespecified probabilitydistribution (which depends on the current state and the selected flaw). However, the recent formu-lation is less flexible than the Moser–Tardos method since it requires a specific flaw selection rule,whereas the algorithm of Moser and Tardos allows an arbitrary rule (and thus can potentially beimplemented more efficiently). We formulate a new “commutativity” condition and prove that it issufficient for an arbitrary rule to work. It also enables an efficient parallelization under an additionalassumption. We then show that existing resampling oracles for perfect matchings and permutationsdo satisfy this condition.

Brief Announcement: Performance prediction for coarse-grained locking - Aksenov, Vitaly; Alistarh, Dan-Adrian; Kuznetsov, Petr (Proceedings of the 2018 ACM Symposium on Principles of Distributed Computing - PODC '18)
A standard design pattern found in many concurrent data structures, such as hash tables or ordered containers, is an alternation of parallelizable sections that incur no data conflicts and critical sections that must run sequentially and are protected with locks. A lock can be viewed as a queue that arbitrates the order in which the critical sections are executed, and a natural question is whether we can use stochastic analysis to predict the resulting throughput. As a preliminary evidence to the affirmative, we describe a simple model that can be used to predict the throughput of coarse-grained lock-based algorithms. We show that our model works well for CLH lock, and we expect it to work for other popular lock designs such as TTAS, MCS, etc.

Bounds on the norm of Wigner-type random matrices - Erdös, László; Mühlbacher, Peter (Random matrices: Theory and applications)
We consider a Wigner-type ensemble, i.e. large hermitian N×N random matrices H=H∗ with centered independent entries and with a general matrix of variances Sxy=𝔼∣∣Hxy∣∣2. The norm of H is asymptotically given by the maximum of the support of the self-consistent density of states. We establish a bound on this maximum in terms of norms of powers of S that substantially improves the earlier bound 2∥S∥1/2∞ given in [O. Ajanki, L. Erdős and T. Krüger, Universality for general Wigner-type matrices, Prob. Theor. Rel. Fields169 (2017) 667–727]. The key element of the proof is an effective Markov chain approximation for the contributions of the weighted Dyck paths appearing in the iterative solution of the corresponding Dyson equation.

Optical functionalization of human class A orphan G-protein-coupled receptors - Morri, Maurizio; Sanchez-Romero, Inmaculada; Tichy, Alexandra-Madelaine; Kainrath, Stephanie; Gerrard, Elliot J.; Hirschfeld, Priscila; Schwarz, Jan; Janovjak, Harald L (Nature Communications)
G-protein-coupled receptors (GPCRs) form the largest receptor family, relay environmental stimuli to changes in cell behavior and represent prime drug targets. Many GPCRs are classified as orphan receptors because of the limited knowledge on their ligands and coupling to cellular signaling machineries. Here, we engineer a library of 63 chimeric receptors that contain the signaling domains of human orphan and understudied GPCRs functionally linked to the light-sensing domain of rhodopsin. Upon stimulation with visible light, we identify activation of canonical cell signaling pathways, including cAMP-, Ca2+-, MAPK/ERK-, and Rho-dependent pathways, downstream of the engineered receptors. For the human pseudogene GPR33, we resurrect a signaling function that supports its hypothesized role as a pathogen entry site. These results demonstrate that substituting unknown chemical activators with a light switch can reveal information about protein function and provide an optically controlled protein library for exploring the physiology and therapeutic potential of understudied GPCRs.

FlexMaps: Computational design of flat flexible shells for shaping 3D objects - Malomo, Luigi; Perez Rodriguez, Jesus; Iarussi, Emmanuel; Pietroni, Nico; Miguel, Eder; Cignoni, Paolo; Bickel, Bernd (ACM Transactions on Graphics)
We propose FlexMaps, a novel framework for fabricating smooth shapes out of flat, flexible panels with tailored mechanical properties. We start by mapping the 3D surface onto a 2D domain as in traditional UV mapping to design a set of deformable flat panels called FlexMaps. For these panels, we design and obtain specific mechanical properties such that, once they are assembled, the static equilibrium configuration matches the desired 3D shape. FlexMaps can be fabricated from an almost rigid material, such as wood or plastic, and are made flexible in a controlled way by using computationally designed spiraling microstructures.

Theory of the rotating polaron: Spectrum and self-localization - Yakaboylu, Enderalp; Midya, Bikashkali; Deuchert, Andreas; Leopold, Nikolai K; Lemeshko, Mikhail (Physical Review B)
We study a quantum impurity possessing both translational and internal rotational degrees of freedom interacting with a bosonic bath. Such a system corresponds to a “rotating polaron,” which can be used to model, e.g., a rotating molecule immersed in an ultracold Bose gas or superfluid helium. We derive the Hamiltonian of the rotating polaron and study its spectrum in the weak- and strong-coupling regimes using a combination of variational, diagrammatic, and mean-field approaches. We reveal how the coupling between linear and angular momenta affects stable quasiparticle states, and demonstrate that internal rotation leads to an enhanced self-localization in the translational degrees of freedom.

Tin diselenide molecular precursor for solution-processable thermoelectric materials - Zhang, Yu; Liu, Yu; Lim, Khak Ho; Xing, Congcong; Li, Mengyao; Zhang, Ting; Tang, Pengyi; Arbiol, Jordi; Llorca, Jordi; Ng, Ka Ming; Ibáñez, Maria; Guardia, Pablo; et al. (Angewandte Chemie International Edition)
In the present work, we detail a fast and simple solution-based method to synthesize hexagonal SnSe2 nanoplates (NPLs) and their use to produce crystallographically textured SnSe2 nanomaterials. We also demonstrate that the same strategy can be used to produce orthorhombic SnSe nanostructures and nanomaterials. NPLs are grown through a screw dislocation-driven mechanism. This mechanism typically results in pyramidal structures, but we demonstrate here that the growth from multiple dislocations results in flower-like structures. Crystallographically textured SnSe2 bulk nanomaterials obtained from the hot pressing of these SnSe2 structures display highly anisotropic charge and heat transport properties and thermoelectric (TE) figures of merit limited by relatively low electrical conductivities. To improve this parameter, SnSe2 NPLs are blended here with metal nanoparticles. The electrical conductivities of the blends are significantly improved with respect to bare SnSe2 NPLs, what translates into a three-fold increase of the TE Figure of merit, reaching unprecedented ZT values up to 0.65.

Exact MAP-inference by confining combinatorial search with LP relaxation - Haller, Stefan; Swoboda, Paul; Savchynskyy, Bogdan (Proceedings of the 32st AAAI Conference on Artificial Intelligence)
We consider the MAP-inference problem for graphical models,which is a valued constraint satisfaction problem defined onreal numbers with a natural summation operation. We proposea family of relaxations (different from the famous Sherali-Adams hierarchy), which naturally define lower bounds for itsoptimum. This family always contains a tight relaxation andwe give an algorithm able to find it and therefore, solve theinitial non-relaxed NP-hard problem.The relaxations we consider decompose the original probleminto two non-overlapping parts: an easy LP-tight part and adifficult one. For the latter part a combinatorial solver must beused. As we show in our experiments, in a number of applica-tions the second, difficult part constitutes only a small fractionof the whole problem. This property allows to significantlyreduce the computational time of the combinatorial solver andtherefore solve problems which were out of reach before.

Josephson effect in a few-hole quantum dot - Ridderbos, Joost; Brauns, Matthias; Shen, Jie; de Vries, Folkert K.; Li, Ang; Bakkers, Erik P. A. M.; Brinkman, Alexander; Zwanenburg, Floris A. (Advanced Materials)
A Ge–Si core–shell nanowire is used to realize a Josephson field‐effect transistor with highly transparent contacts to superconducting leads. By changing the electric field, access to two distinct regimes, not combined before in a single device, is gained: in the accumulation mode the device is highly transparent and the supercurrent is carried by multiple subbands, while near depletion, the supercurrent is carried by single‐particle levels of a strongly coupled quantum dot operating in the few‐hole regime. These results establish Ge–Si nanowires as an important platform for hybrid superconductor–semiconductor physics and Majorana fermions.

Genome amplification and cellular senescence are hallmarks of human placenta development - Velicky, Philipp; Meinhardt, Gudrun; Plessl, Kerstin; Vondra, Sigrid; Weiss, Tamara; Haslinger, Peter; Lendl, Thomas; Aumayr, Karin; Mairhofer, Mario; Zhu, Xiaowei; Schütz, Birgit; Hannibal, Roberta L.; et al. (PLOS Genetics)
Genome amplification and cellular senescence are commonly associated with pathological processes. While physiological roles for polyploidization and senescence have been described in mouse development, controversy exists over their significance in humans. Here, we describe tetraploidization and senescence as phenomena of normal human placenta development. During pregnancy, placental extravillous trophoblasts (EVTs) invade the pregnant endometrium, termed decidua, to establish an adapted microenvironment required for the developing embryo. This process is critically dependent on continuous cell proliferation and differentiation, which is thought to follow the classical model of cell cycle arrest prior to terminal differentiation. Strikingly, flow cytometry and DNAseq revealed that EVT formation is accompanied with a genome-wide polyploidization, independent of mitotic cycles. DNA replication in these cells was analysed by a fluorescent cell-cycle indicator reporter system, cell cycle marker expression and EdU incorporation. Upon invasion into the decidua, EVTs widely lose their replicative potential and enter a senescent state characterized by high senescence-associated (SA) β-galactosidase activity, induction of a SA secretory phenotype as well as typical metabolic alterations. Furthermore, we show that the shift from endocycle-dependent genome amplification to growth arrest is disturbed in androgenic complete hydatidiform moles (CHM), a hyperplastic pregnancy disorder associated with increased risk of developing choriocarinoma. Senescence is decreased in CHM-EVTs, accompanied by exacerbated endoreduplication and hyperploidy. We propose induction of cellular senescence as a ploidy-limiting mechanism during normal human placentation and unravel a link between excessive polyploidization and reduced senescence in CHM.

Self-consistency test reveals systematic bias in programs for prediction change of stability upon mutation - Usmanova, Dinara R; Bogatyreva, Natalya S; Ariño Bernad, Joan; Eremina, Aleksandra A; Gorshkova, Anastasiya A; Kanevskiy, German M; Lonishin, Lyubov R; Meister, Alexander V; Yakupova, Alisa G; Kondrashov, Fyodor; Ivankov, Dmitry (Bioinformatics)
Motivation Computational prediction of the effect of mutations on protein stability is used by researchers in many fields. The utility of the prediction methods is affected by their accuracy and bias. Bias, a systematic shift of the predicted change of stability, has been noted as an issue for several methods, but has not been investigated systematically. Presence of the bias may lead to misleading results especially when exploring the effects of combination of different mutations. Results Here we use a protocol to measure the bias as a function of the number of introduced mutations. It is based on a self-consistency test of the reciprocity the effect of a mutation. An advantage of the used approach is that it relies solely on crystal structures without experimentally measured stability values. We applied the protocol to four popular algorithms predicting change of protein stability upon mutation, FoldX, Eris, Rosetta and I-Mutant, and found an inherent bias. For one program, FoldX, we manage to substantially reduce the bias using additional relaxation by Modeller. Authors using algorithms for predicting effects of mutations should be aware of the bias described here.

On the relation between filament density, force generation, and protrusion rate in mesenchymal cell motility - Dolati, Setareh; Kage, Frieda; Mueller, Jan; Müsken, Mathias; Kirchner, Marieluise; Dittmar, Gunnar; Sixt, Michael K; Rottner, Klemens; Falcke, Martin (Molecular Biology of the Cell)
Lamellipodia are flat membrane protrusions formed during mesenchymal motion. Polymerization at the leading edge assembles the actin filament network and generates protrusion force. How this force is supported by the network and how the assembly rate is shared between protrusion and network retrograde flow determines the protrusion rate. We use mathematical modeling to understand experiments changing the F-actin density in lamellipodia of B16-F1 melanoma cells by modulation of Arp2/3 complex activity or knockout of the formins FMNL2 and FMNL3. Cells respond to a reduction of density with a decrease of protrusion velocity, an increase in the ratio of force to filament number, but constant network assembly rate. The relation between protrusion force and tension gradient in the F-actin network and the density dependency of friction, elasticity, and viscosity of the network explain the experimental observations. The formins act as filament nucleators and elongators with differential rates. Modulation of their activity suggests an effect on network assembly rate. Contrary to these expectations, the effect of changes in elongator composition is much weaker than the consequences of the density change. We conclude that the force acting on the leading edge membrane is the force required to drive F-actin network retrograde flow.

“Shepherd’s crook” neurons drive and synchronize the enhancing and suppressive mechanisms of the midbrain stimulus selection network - Garrido-Charad, Florencia; Vega Zuniga, Tomas A; Gutiérrez-Ibáñez, Cristián; Fernandez, Pedro; López-Jury, Luciana; González-Cabrera, Cristian; Karten, Harvey J.; Luksch, Harald; Marín, Gonzalo J. (Proceedings of the National Academy of Sciences)
The optic tectum (TeO), or superior colliculus, is a multisensory midbrain center that organizes spatially orienting responses to relevant stimuli. To define the stimulus with the highest priority at each moment, a network of reciprocal connections between the TeO and the isthmi promotes competition between concurrent tectal inputs. In the avian midbrain, the neurons mediating enhancement and suppression of tectal inputs are located in separate isthmic nuclei, facilitating the analysis of the neural processes that mediate competition. A specific subset of radial neurons in the intermediate tectal layers relay retinal inputs to the isthmi, but at present it is unclear whether separate neurons innervate individual nuclei or a single neural type sends a common input to several of them. In this study, we used in vitro neural tracing and cell-filling experiments in chickens to show that single neurons innervate, via axon collaterals, the three nuclei that comprise the isthmotectal network. This demonstrates that the input signals representing the strength of the incoming stimuli are simultaneously relayed to the mechanisms promoting both enhancement and suppression of the input signals. By performing in vivo recordings in anesthetized chicks, we also show that this common input generates synchrony between both antagonistic mechanisms, demonstrating that activity enhancement and suppression are closely coordinated. From a computational point of view, these results suggest that these tectal neurons constitute integrative nodes that combine inputs from different sources to drive in parallel several concurrent neural processes, each performing complementary functions within the network through different firing patterns and connectivity.

State of the art on stylized fabrication - Bickel, Bernd; Cignoni, Paolo; Malomo, Luigi; Pietroni, Nico (Computer Graphics Forum)
Digital fabrication devices are powerful tools for creating tangible reproductions of 3D digital models. Most available printing technologies aim at producing an accurate copy of a tridimensional shape. However, fabrication technologies can also be used to create a stylistic representation of a digital shape. We refer to this class of methods as ‘stylized fabrication methods’. These methods abstract geometric and physical features of a given shape to create an unconventional representation, to produce an optical illusion or to devise a particular interaction with the fabricated model. In this state‐of‐the‐art report, we classify and overview this broad and emerging class of approaches and also propose possible directions for future research.

The Bogoliubov free energy functional I: Existence of minimizers and phase diagram - Napiórkowski, Marcin M; Reuvers, Robin; Solovej, Jan Philip (Archive for Rational Mechanics and Analysis)
The Bogoliubov free energy functional is analysed. The functional serves as a model of a translation-invariant Bose gas at positive temperature. We prove the existence of minimizers in the case of repulsive interactions given by a sufficiently regular two-body potential. Furthermore, we prove the existence of a phase transition in this model and provide its phase diagram.

The critical point of the transition to turbulence in pipe flow - Vasudevan, Mukund; Hof, Björn (Journal of Fluid Mechanics)
In pipes, turbulence sets in despite the linear stability of the laminar Hagen–Poiseuille flow. The Reynolds number ( ) for which turbulence first appears in a given experiment – the ‘natural transition point’ – depends on imperfections of the set-up, or, more precisely, on the magnitude of finite amplitude perturbations. At onset, turbulence typically only occupies a certain fraction of the flow, and this fraction equally is found to differ from experiment to experiment. Despite these findings, Reynolds proposed that after sufficiently long times, flows may settle to steady conditions: below a critical velocity, flows should (regardless of initial conditions) always return to laminar, while above this velocity, eddying motion should persist. As will be shown, even in pipes several thousand diameters long, the spatio-temporal intermittent flow patterns observed at the end of the pipe strongly depend on the initial conditions, and there is no indication that different flow patterns would eventually settle to a (statistical) steady state. Exploiting the fact that turbulent puffs do not age (i.e. they are memoryless), we continuously recreate the puff sequence exiting the pipe at the pipe entrance, and in doing so introduce periodic boundary conditions for the puff pattern. This procedure allows us to study the evolution of the flow patterns for arbitrary long times, and we find that after times in excess of advective time units, indeed a statistical steady state is reached. Although the resulting flows remain spatio-temporally intermittent, puff splitting and decay rates eventually reach a balance, so that the turbulent fraction fluctuates around a well-defined level which only depends on . In accordance with Reynolds’ proposition, we find that at lower (here 2020), flows eventually always resume to laminar, while for higher ( ), turbulence persists. The critical point for pipe flow hence falls in the interval of $2020 , which is in very good agreement with the recently proposed value of . The latter estimate was based on single-puff statistics and entirely neglected puff interactions. Unlike in typical contact processes where such interactions strongly affect the percolation threshold, in pipe flow, the critical point is only marginally influenced. Interactions, on the other hand, are responsible for the approach to the statistical steady state. As shown, they strongly affect the resulting flow patterns, where they cause ‘puff clustering’, and these regions of large puff densities are observed to travel across the puff pattern in a wave-like fashion.

Algorithmic analysis of qualitative and quantitative termination problems for affine probabilistic programs - Chatterjee, Krishnendu; Fu, Hongfei; Novotný, Petr; Hasheminezhad, Rouzbeh (ACM Transactions on Programming Languages and Systems)
In this article, we consider the termination problem of probabilistic programs with real-valued variables. Thequestions concerned are: qualitative ones that ask (i) whether the program terminates with probability 1(almost-sure termination) and (ii) whether the expected termination time is finite (finite termination); andquantitative ones that ask (i) to approximate the expected termination time (expectation problem) and (ii) tocompute a boundBsuch that the probability not to terminate afterBsteps decreases exponentially (con-centration problem). To solve these questions, we utilize the notion of ranking supermartingales, which isa powerful approach for proving termination of probabilistic programs. In detail, we focus on algorithmicsynthesis of linear ranking-supermartingales over affine probabilistic programs (Apps) with both angelic anddemonic non-determinism. An important subclass of Apps is LRApp which is defined as the class of all Appsover which a linear ranking-supermartingale exists.Our main contributions are as follows. Firstly, we show that the membership problem of LRApp (i) canbe decided in polynomial time for Apps with at most demonic non-determinism, and (ii) isNP-hard and inPSPACEfor Apps with angelic non-determinism. Moreover, theNP-hardness result holds already for Appswithout probability and demonic non-determinism. Secondly, we show that the concentration problem overLRApp can be solved in the same complexity as for the membership problem of LRApp. Finally, we show thatthe expectation problem over LRApp can be solved in2EXPTIMEand isPSPACE-hard even for Apps withoutprobability and non-determinism (i.e., deterministic programs). Our experimental results demonstrate theeffectiveness of our approach to answer the qualitative and quantitative questions over Apps with at mostdemonic non-determinism.

The cohomological Hall algebra of a preprojective algebra - Yang, Yaping; Zhao, Gufang (Proceedings of the London Mathematical Society)
We introduce for each quiver Q and each algebraic oriented cohomology theory A, the cohomological Hall algebra (CoHA) of Q, as the A-homology of the moduli of representations of the preprojective algebra of Q. This generalizes the K-theoretic Hall algebra of commuting varieties defined by Schiffmann-Vasserot. When A is the Morava K-theory, we show evidence that this algebra is a candidate for Lusztig's reformulated conjecture on modular representations of algebraic groups. We construct an action of the preprojective CoHA on the A-homology of Nakajima quiver varieties. We compare this with the action of the Borel subalgebra of Yangian when A is the intersection theory. We also give a shuffle algebra description of this CoHA in terms of the underlying formal group law of A. As applications, we obtain a shuffle description of the Yangian.

Parent-of-Origin-Dependent Gene Expression in Male and Female Schistosome Parasites - Kincaid-Smith, Julien; Picard, Marion A L; Cosseau, Céline; Boissier, Jérôme; Severac, Dany; Grunau, Christoph; Toulza, Eve (Genome Biology and Evolution)
Schistosomes are the causative agents of schistosomiasis, a neglected tropical disease affecting over 230 million people worldwide.Additionally to their major impact on human health, they are also models of choice in evolutionary biology. These parasitic flatwormsare unique among the common hermaphroditic trematodes as they have separate sexes. This so-called “evolutionary scandal”displays a female heterogametic genetic sex-determination system (ZZ males and ZW females), as well as a pronounced adult sexualdimorphism. These phenotypic differences are determined by a shared set of genes in both sexes, potentially leading to intralocussexual conflicts. To resolve these conflicts in sexually selected traits, molecular mechanisms such as sex-biased gene expression couldoccur, but parent-of-origin gene expression also provides an alternative. In this work we investigated the latter mechanism, that is,genes expressed preferentially from either the maternal or the paternal allele, inSchistosoma mansonispecies. To this end, tran-scriptomes from male and female hybrid adults obtained by strain crosses were sequenced. Strain-specific single nucleotide poly-morphism (SNP) markers allowed us to discriminate the parental origin, while reciprocal crosses helped to differentiate parentalexpression from strain-specific expression. We identified genes containing SNPs expressed in a parent-of-origin manner consistentwith paternal and maternal imprints. Although the majority of the SNPs was identified in mitochondrial and Z-specific loci, theremaining SNPs found in male and female transcriptomes were situated in genes that have the potential to explain sexual differencesin schistosome parasites. Furthermore, we identified and validated four new Z-specific scaffolds.

Goal-HSVI: Heuristic search value iteration for goal-POMDPs - Horák, Karel; Bošanský, Branislav; Chatterjee, Krishnendu (Proceedings of the Twenty-Seventh International Joint Conference on Artificial Intelligence)
Partially observable Markov decision processes (POMDPs) are the standard models for planning under uncertainty with both finite and infinite horizon. Besides the well-known discounted-sum objective, indefinite-horizon objective (aka Goal-POMDPs) is another classical objective for POMDPs. In this case, given a set of target states and a positive cost for each transition, the optimization objective is to minimize the expected total cost until a target state is reached. In the literature, RTDP-Bel or heuristic search value iteration (HSVI) have been used for solving Goal-POMDPs. Neither of these algorithms has theoretical convergence guarantees, and HSVI may even fail to terminate its trials. We give the following contributions: (1) We discuss the challenges introduced in Goal-POMDPs and illustrate how they prevent the original HSVI from converging. (2) We present a novel algorithm inspired by HSVI, termed Goal-HSVI, and show that our algorithm has convergence guarantees. (3) We show that Goal-HSVI outperforms RTDP-Bel on a set of well-known examples.

Expectation optimization with probabilistic guarantees in POMDPs with discounted-sum objectives - Chatterjee, Krishnendu; Elgyütt, Adrian; Novotny, Petr; Rouillé, Owen
Partially-observable Markov decision processes (POMDPs) with discounted-sum payoff are a standard framework to model a wide range of problems related to decision making under uncertainty. Traditionally, the goal has been to obtain policies that optimize the expectation of the discounted-sum payoff. A key drawback of the expectation measure is that even low probability events with extreme payoff can significantly affect the expectation, and thus the obtained policies are not necessarily risk-averse. An alternate approach is to optimize the probability that the payoff is above a certain threshold, which allows obtaining risk-averse policies, but ignores optimization of the expectation. We consider the expectation optimization with probabilistic guarantee (EOPG) problem, where the goal is to optimize the expectation ensuring that the payoff is above a given threshold with at least a specified probability. We present several results on the EOPG problem, including the first algorithm to solve it.

Sensor synthesis for POMDPs with reachability objectives - Chatterjee, Krishnendu; Chemlík, Martin; Topcu, Ufuk
Partially observable Markov decision processes (POMDPs) are widely used in probabilistic planning problems in which an agent interacts with an environment using noisy and imprecise sensors. We study a setting in which the sensors are only partially defined and the goal is to synthesize “weakest” additional sensors, such that in the resulting POMDP, there is a small-memory policy for the agent that almost-surely (with probability 1) satisfies a reachability objective. We show that the problem is NP-complete, and present a symbolic algorithm by encoding the problem into SAT instances. We illustrate trade-offs between the amount of memory of the policy and the number of additional sensors on a simple example. We have implemented our approach and consider three classical POMDP examples from the literature, and show that in all the examples the number of sensors can be significantly decreased (as compared to the existing solutions in the literature) without increasing the complexity of the policies.

Superconcentrators of density 25.3 - Kolmogorov, Vladimir; Rolinek, Michal (Ars Combinatoria)
An N-superconcentrator is a directed, acyclic graph with N input nodes and N output nodes such that every subset of the inputs and every subset of the outputs of same cardinality can be connected by node-disjoint paths. It is known that linear-size and bounded-degree superconcentrators exist. We prove the existence of such superconcentrators with asymptotic density 25.3 (where the density is the number of edges divided by N). The previously best known densities were 28 [12] and 27.4136 [17].

Any cyclic quadrilateral can be inscribed in any closed convex smooth curve - Akopyan, Arseniy; Avvakumov, Sergey (Forum of Mathematics, Sigma)
We prove that any cyclic quadrilateral can be inscribed in any closed convex C1-curve. The smoothness condition is not required if the quadrilateral is a rectangle.

SpaceMint: A cryptocurrency based on proofs of space - Park, Sunoo; Kwon, Albert; Fuchsbauer, Georg; Gazi, Peter; Alwen, Joel F; Pietrzak, Krzysztof Z (22nd International Conference on Financial Cryptography and Data Security)
Bitcoin has become the most successful cryptocurrency ever deployed, and its most distinctive feature is that it is decentralized. Its underlying protocol (Nakamoto consensus) achieves this by using proof of work, which has the drawback that it causes the consumption of vast amounts of energy to maintain the ledger. Moreover, Bitcoin mining dynamics have become less distributed over time. Towards addressing these issues, we propose SpaceMint, a cryptocurrency based on proofs of space instead of proofs of work. Miners in SpaceMint dedicate disk space rather than computation. We argue that SpaceMint’s design solves or alleviates several of Bitcoin’s issues: most notably, its large energy consumption. SpaceMint also rewards smaller miners fairly according to their contribution to the network, thus incentivizing more distributed participation. This paper adapts proof of space to enable its use in cryptocurrency, studies the attacks that can arise against a Bitcoin-like blockchain that uses proof of space, and proposes a new blockchain format and transaction types to address these attacks. Our prototype shows that initializing 1 TB for mining takes about a day (a one-off setup cost), and miners spend on average just a fraction of a second per block mined. Finally, we provide a game-theoretic analysis modeling SpaceMint as an extensive game (the canonical game-theoretic notion for games that take place over time) and show that this stylized game satisfies a strong equilibrium notion, thereby arguing for SpaceMint ’s stability and consensus.

The Rho regulator Myosin IXb enables nonlymphoid tissue seeding of protective CD8+T cells - Moalli, Federica; Ficht, Xenia; Germann, Philipp; Vladymyrov, Mykhailo; Stolp, Bettina; de Vries, Ingrid; Lyck, Ruth; Balmer, Jasmin; Fiocchi, Amleto; Kreutzfeldt, Mario; Merkler, Doron; Iannacone, Matteo; et al. (The Journal of Experimental Medicine)
T cells are actively scanning pMHC-presenting cells in lymphoid organs and nonlymphoid tissues (NLTs) with divergent topologies and confinement. How the T cell actomyosin cytoskeleton facilitates this task in distinct environments is incompletely understood. Here, we show that lack of Myosin IXb (Myo9b), a negative regulator of the small GTPase Rho, led to increased Rho-GTP levels and cell surface stiffness in primary T cells. Nonetheless, intravital imaging revealed robust motility of Myo9b−/− CD8+ T cells in lymphoid tissue and similar expansion and differentiation during immune responses. In contrast, accumulation of Myo9b−/− CD8+ T cells in NLTs was strongly impaired. Specifically, Myo9b was required for T cell crossing of basement membranes, such as those which are present between dermis and epidermis. As consequence, Myo9b−/− CD8+ T cells showed impaired control of skin infections. In sum, we show that Myo9b is critical for the CD8+ T cell adaptation from lymphoid to NLT surveillance and the establishment of protective tissue–resident T cell populations.

X10 expansion microscopy enables 25‐nm resolution on conventional microscopes - Truckenbrodt, Sven M; Maidorn, Manuel; Crzan, Dagmar; Wildhagen, Hanna; Kabatas, Selda; Rizzoli, Silvio O (EMBO reports)
Expansion microscopy is a recently introduced imaging technique that achieves super‐resolution through physically expanding the specimen by ~4×, after embedding into a swellable gel. The resolution attained is, correspondingly, approximately fourfold better than the diffraction limit, or ~70 nm. This is a major improvement over conventional microscopy, but still lags behind modern STED or STORM setups, whose resolution can reach 20–30 nm. We addressed this issue here by introducing an improved gel recipe that enables an expansion factor of ~10× in each dimension, which corresponds to an expansion of the sample volume by more than 1,000‐fold. Our protocol, which we termed X10 microscopy, achieves a resolution of 25–30 nm on conventional epifluorescence microscopes. X10 provides multi‐color images similar or even superior to those produced with more challenging methods, such as STED, STORM, and iterative expansion microscopy (iExM). X10 is therefore the cheapest and easiest option for high‐quality super‐resolution imaging currently available. X10 should be usable in any laboratory, irrespective of the machinery owned or of the technical knowledge.

Space-optimal majority in population protocols - Alistarh, Dan-Adrian; Aspnes, James; Gelashvili, Rati (Proceedings of the 29th Annual ACM-SIAM Symposium on Discrete Algorithms)
Population protocols are a popular model of distributed computing, in which n agents with limited local state interact randomly, and cooperate to collectively compute global predicates. Inspired by recent developments in DNA programming, an extensive series of papers, across different communities, has examined the computability and complexity characteristics of this model. Majority, or consensus, is a central task in this model, in which agents need to collectively reach a decision as to which one of two states A or B had a higher initial count. Two metrics are important: the time that a protocol requires to stabilize to an output decision, and the state space size that each agent requires to do so. It is known that majority requires Ω(log log n) states per agent to allow for fast (poly-logarithmic time) stabilization, and that O(log2 n) states are sufficient. Thus, there is an exponential gap between the space upper and lower bounds for this problem. This paper addresses this question. On the negative side, we provide a new lower bound of Ω(log n) states for any protocol which stabilizes in O(n1–c) expected time, for any constant c > 0. This result is conditional on monotonicity and output assumptions, satisfied by all known protocols. Technically, it represents a departure from previous lower bounds, in that it does not rely on the existence of dense configurations. Instead, we introduce a new generalized surgery technique to prove the existence of incorrect executions for any algorithm which would contradict the lower bound. Subsequently, our lower bound also applies to general initial configurations, including ones with a leader. On the positive side, we give a new algorithm for majority which uses O(log n) states, and stabilizes in O(log2 n) expected time. Central to the algorithm is a new leaderless phase clock technique, which allows agents to synchronize in phases of Θ(n log n) consecutive interactions using O(log n) states per agent, exploiting a new connection between population protocols and power-of-two-choices load balancing mechanisms. We also employ our phase clock to build a leader election algorithm with a state space of size O(log n), which stabilizes in O(log2 n) expected time.

Clines on the seashore: The genomic architecture underlying rapid divergence in the face of gene flow - Westram, Anja M; Rafajlović, Marina; Chaube, Pragya; Faria, Rui; Larsson, Tomas; Panova, Marina; Ravinet, Mark; Blomberg, Anders; Mehlig, Bernhard; Johannesson, Kerstin; Butlin, Roger (Evolution Letters)
Adaptive divergence and speciation may happen despite opposition by gene flow. Identifying the genomic basis underlying divergence with gene flow is a major task in evolutionary genomics. Most approaches (e.g., outlier scans) focus on genomic regions of high differentiation. However, not all genomic architectures potentially underlying divergence are expected to show extreme differentiation. Here, we develop an approach that combines hybrid zone analysis (i.e., focuses on spatial patterns of allele frequency change) with system-specific simulations to identify loci inconsistent with neutral evolution. We apply this to a genome-wide SNP set from an ideally suited study organism, the intertidal snail Littorina saxatilis, which shows primary divergence between ecotypes associated with different shore habitats. We detect many SNPs with clinal patterns, most of which are consistent with neutrality. Among non-neutral SNPs, most are located within three large putative inversions differentiating ecotypes. Many non-neutral SNPs show relatively low levels of differentiation. We discuss potential reasons for this pattern, including loose linkage to selected variants, polygenic adaptation and a component of balancing selection within populations (which may be expected for inversions). Our work is in line with theory predicting a role for inversions in divergence, and emphasizes that genomic regions contributing to divergence may not always be accessible with methods purely based on allele frequency differences. These conclusions call for approaches that take spatial patterns of allele frequency change into account in other systems.

Are assortative mating and genital divergence driven by reinforcement? - Hollander, Johan; Montaño-Rendón, Mauricio; Bianco, Giuseppe; Yang, Xi; Westram, Anja M; Duvaux, Ludovic; Reid, David G.; Butlin, Roger K. (Evolution Letters)
The evolution of assortative mating is a key part of the speciation process. Stronger assortment, or greater divergence in mating traits, between species pairs with overlapping ranges is commonly observed, but possible causes of this pattern of reproductive character displacement are difficult to distinguish. We use a multidisciplinary approach to provide a rare example where it is possible to distinguish among hypotheses concerning the evolution of reproductive character displacement. We build on an earlier comparative analysis that illustrated a strong pattern of greater divergence in penis form between pairs of sister species with overlapping ranges than between allopatric sister-species pairs, in a large clade of marine gastropods (Littorinidae). We investigate both assortative mating and divergence in male genitalia in one of the sister-species pairs, discriminating among three contrasting processes each of which can generate a pattern of reproductive character displacement: reinforcement, reproductive interference and the Templeton effect. We demonstrate reproductive character displacement in assortative mating, but not in genital form between this pair of sister species and use demographic models to distinguish among the different processes. Our results support a model with no gene flow since secondary contact and thus favor reproductive interference as the cause of reproductive character displacement for mate choice, rather than reinforcement. High gene flow within species argues against the Templeton effect. Secondary contact appears to have had little impact on genital divergence.

Novel reversibly switchable fluorescent proteins for RESOLFT and STED nanoscopy engineered from the bacterial photoreceptor YtvA - Gregor, Carola; Sidenstein, Sven C.; Andresen, Martin; Sahl, Steffen J.; Danzl, Johann G; Hell, Stefan W. (Scientific Reports)
The reversibly switchable fluorescent proteins (RSFPs) commonly used for RESOLFT nanoscopy have been developed from fluorescent proteins of the GFP superfamily. These proteins are bright, but exhibit several drawbacks such as relatively large size, oxygen-dependence, sensitivity to low pH, and limited switching speed. Therefore, RSFPs from other origins with improved properties need to be explored. Here, we report the development of two RSFPs based on the LOV domain of the photoreceptor protein YtvA from Bacillus subtilis. LOV domains obtain their fluorescence by association with the abundant cellular cofactor flavin mononucleotide (FMN). Under illumination with blue and ultraviolet light, they undergo a photocycle, making these proteins inherently photoswitchable. Our first improved variant, rsLOV1, can be used for RESOLFT imaging, whereas rsLOV2 proved useful for STED nanoscopy of living cells with a resolution of down to 50 nm. In addition to their smaller size compared to GFP-related proteins (17 kDa instead of 27 kDa) and their usability at low pH, rsLOV1 and rsLOV2 exhibit faster switching kinetics, switching on and off 3 times faster than rsEGFP2, the fastest-switching RSFP reported to date. Therefore, LOV-domain-based RSFPs have potential for applications where the switching speed of GFP-based proteins is limiting.
Keywords: Multidisciplinary

Significance of whole-genome duplications on the emergence of evolutionary novelties - Yuuta, Moriyama; Koshiba-Takeuchi, Kazuko (Briefings in Functional Genomics)
Acquisition of evolutionary novelties is a fundamental process for adapting to the external environment and invading new niches and results in the diversification of life, which we can see in the world today. How such novel phenotypic traits are acquired in the course of evolution and are built up in developing embryos has been a central question in biology. Whole-genome duplication (WGD) is a process of genome doubling that supplies raw genetic materials and increases genome complexity. Recently, it has been gradually revealed that WGD and subsequent fate changes of duplicated genes can facilitate phenotypic evolution. Here, we review the current understanding of the relationship between WGD and the acquisition of evolutionary novelties. We show some examples of this link and discuss how WGD and subsequent duplicated genes can facilitate phenotypic evolution as well as when such genomic doubling can be advantageous for adaptation.
Keywords: Genetics; Molecular Biology; Biochemistry; General Medicine

Data from: Clines on the seashore: the genomic architecture underlying rapid divergence in the face of gene flow - Westram, Anja M; Rafajlović, Marina; Chaube, Pragya; Faria, Rui; Larsson, Tomas; Panova, Marina; Ravinet, Mark; Blomberg, Anders; Mehlig, Bernhard; Johannesson, Kerstin; Butlin, Roger
Adaptive divergence and speciation may happen despite opposition by gene flow. Identifying the genomic basis underlying divergence with gene flow is a major task in evolutionary genomics. Most approaches (e.g. outlier scans) focus on genomic regions of high differentiation. However, not all genomic architectures potentially underlying divergence are expected to show extreme differentiation. Here, we develop an approach that combines hybrid zone analysis (i.e. focuses on spatial patterns of allele frequency change) with system-specific simulations to identify loci inconsistent with neutral evolution. We apply this to a genome-wide SNP set from an ideally-suited study organism, the intertidal snail Littorina saxatilis, which shows primary divergence between ecotypes associated with different shore habitats. We detect many SNPs with clinal patterns, most of which are consistent with neutrality. Among non-neutral SNPs, most are located within three large putative inversions differentiating ecotypes. Many non-neutral SNPs show relatively low levels of differentiation. We discuss potential reasons for this pattern, including loose linkage to selected variants, polygenic adaptation and a component of balancing selection within populations (which may be expected for inversions). Our work is in line with theory predicting a role for inversions in divergence, and emphasises that genomic regions contributing to divergence may not always be accessible with methods purely based on allele frequency differences. These conclusions call for approaches that take spatial patterns of allele frequency change into account in other systems.

Data from: Are assortative mating and genital divergence driven by reinforcement? - Hollander, Johan; Montaño-Rendón, Mauricio; Bianco, Giuseppe; Yang, Xi; Westram, Anja M; Duvaux, Ludovic; Reid, David G.; Butlin, Roger K.
The evolution of assortative mating is a key part of the speciation process. Stronger assortment, or greater divergence in mating traits, between species pairs with overlapping ranges is commonly observed, but possible causes of this pattern of reproductive character displacement are difficult to distinguish. We use a multidisciplinary approach to provide a rare example where it is possible to distinguish among hypotheses concerning the evolution of reproductive character displacement. We build on an earlier comparative analysis that illustrated a strong pattern of greater divergence in penis form between pairs of sister species with overlapping ranges than between allopatric sister-species pairs, in a large clade of marine gastropods (Littorinidae). We investigate both assortative mating and divergence in male genitalia in one of the sister-species pairs, discriminating among three contrasting processes each of which can generate a pattern of reproductive character displacement: reinforcement, reproductive interference and the Templeton effect. We demonstrate reproductive character displacement in assortative mating, but not in genital form between this pair of sister species and use demographic models to distinguish among the different processes. Our results support a model with no gene flow since secondary contact and thus favour reproductive interference as the cause of reproductive character displacement for mate choice, rather than reinforcement. High gene flow within species argues against the Templeton effect. Secondary contact appears to have had little impact on genital divergence.

Learning intelligent dialogs for bounding box annotation - Uijlings, Jasper; Konyushkova, Ksenia; Lampert, Christoph; Ferrari, Vittorio (2018 IEEE/CVF Conference on Computer Vision and Pattern Recognition)
We introduce Intelligent Annotation Dialogs for bounding box annotation. We train an agent to automatically choose a sequence of actions for a human annotator to produce a bounding box in a minimal amount of time. Specifically, we consider two actions: box verification [34], where the annotator verifies a box generated by an object detector, and manual box drawing. We explore two kinds of agents, one based on predicting the probability that a box will be positively verified, and the other based on reinforcement learning. We demonstrate that (1) our agents are able to learn efficient annotation strategies in several scenarios, automatically adapting to the image difficulty, the desired quality of the boxes, and the detector strength; (2) in all scenarios the resulting annotation dialogs speed up annotation compared to manual box drawing alone and box verification alone, while also outperforming any fixed combination of verification and drawing in most scenarios; (3) in a realistic scenario where the detector is iteratively re-trained, our agents evolve a series of strategies that reflect the shifting trade-off between verification and drawing as the detector grows stronger.

Byzantine stochastic gradient descent - Alistarh, Dan-Adrian; Allen-Zhu, Zeyuan; Li, Jerry (Advances in Neural Information Processing Systems)
This paper studies the problem of distributed stochastic optimization in an adversarial setting where, out of m machines which allegedly compute stochastic gradients every iteration, an α-fraction are Byzantine, and may behave adversarially. Our main result is a variant of stochastic gradient descent (SGD) which finds ε-approximate minimizers of convex functions in T=O~(1/ε²m+α²/ε²) iterations. In contrast, traditional mini-batch SGD needs T=O(1/ε²m) iterations, but cannot tolerate Byzantine failures. Further, we provide a lower bound showing that, up to logarithmic factors, our algorithm is information-theoretically optimal both in terms of sample complexity and time complexity.

Even delta-matroids and the complexity of planar boolean CSPs - Kazda, Alexandr; Kolmogorov, Vladimir; Rolinek, Michal (ACM Transactions on Algorithms)
The main result of this article is a generalization of the classical blossom algorithm for finding perfect matchings. Our algorithm can efficiently solve Boolean CSPs where each variable appears in exactly two constraints (we call it edge CSP) and all constraints are even Δ-matroid relations (represented by lists of tuples). As a consequence of this, we settle the complexity classification of planar Boolean CSPs started by Dvorak and Kupec. Using a reduction to even Δ-matroids, we then extend the tractability result to larger classes of Δ-matroids that we call efficiently coverable. It properly includes classes that were known to be tractable before, namely, co-independent, compact, local, linear, and binary, with the following caveat:We represent Δ-matroids by lists of tuples, while the last two use a representation by matrices. Since an n ×n matrix can represent exponentially many tuples, our tractability result is not strictly stronger than the known algorithm for linear and binary Δ-matroids.

Inferring recent demography from spatial genetic structure - Ringbauer, Harald
This thesis is concerned with the inference of current population structure based on geo-referenced genetic data. The underlying idea is that population structure affects its spatial genetic structure. Therefore, genotype information can be utilized to estimate important demographic parameters such as migration rates. These indirect estimates of population structure have become very attractive, as genotype data is now widely available. However, there also has been much concern about these approaches. Importantly, genetic structure can be influenced by many complex patterns, which often cannot be disentangled. Moreover, many methods merely fit heuristic patterns of genetic structure, and do not build upon population genetics theory. Here, I describe two novel inference methods that address these shortcomings. In Chapter 2, I introduce an inference scheme based on a new type of signal, identity by descent (IBD) blocks. Recently, it has become feasible to detect such long blocks of genome shared between pairs of samples. These blocks are direct traces of recent coalescence events. As such, they contain ample signal for inferring recent demography. I examine sharing of IBD blocks in two-dimensional populations with local migration. Using a diffusion approximation, I derive formulas for an isolation by distance pattern of long IBD blocks and show that sharing of long IBD blocks approaches rapid exponential decay for growing sample distance. I describe an inference scheme based on these results. It can robustly estimate the dispersal rate and population density, which is demonstrated on simulated data. I also show an application to estimate mean migration and the rate of recent population growth within Eastern Europe. Chapter 3 is about a novel method to estimate barriers to gene flow in a two dimensional population. This inference scheme utilizes geographically localized allele frequency fluctuations - a classical isolation by distance signal. The strength of these local fluctuations increases on average next to a barrier, and there is less correlation across it. I again use a framework of diffusion of ancestral lineages to model this effect, and provide an efficient numerical implementation to fit the results to geo-referenced biallelic SNP data. This inference scheme is able to robustly estimate strong barriers to gene flow, as tests on simulated data confirm.

On the circle covering theorem by A.W. Goodman and R.E. Goodman - Akopyan, Arseniy; Balitskiy, Alexey; Grigorev, Mikhail (Discrete & Computational Geometry)
In 1945, A.W. Goodman and R.E. Goodman proved the following conjecture by P. Erdős: Given a family of (round) disks of radii r1, … , rn in the plane, it is always possible to cover them by a disk of radius R= ∑ ri, provided they cannot be separated into two subfamilies by a straight line disjoint from the disks. In this note we show that essentially the same idea may work for different analogues and generalizations of their result. In particular, we prove the following: Given a family of positive homothetic copies of a fixed convex body K⊂ Rd with homothety coefficients τ1, … , τn> 0 , it is always possible to cover them by a translate of d+12(∑τi)K, provided they cannot be separated into two subfamilies by a hyperplane disjoint from the homothets.

Optical and optogenetic control of proliferation and survival - Gschaider-Reichhart, Eva
The aim of this thesis was the development of new strategies for optical and optogenetic control of proliferative and pro-survival signaling, and characterizing them from the molecular mechanism up to cellular effects. These new light-based methods have unique features, such as red light as an activator, or the avoidance of gene delivery, which enable to overcome current limitations, such as light delivery to target tissues and feasibility as therapeutic approach. A special focus was placed on implementing these new light-based approaches in pancreatic β-cells, as β-cells are the key players in diabetes and especially their loss in number negatively affects disease progression. Currently no treatment options are available to compensate the lack of functional β-cells in diabetic patients. In a first approach, red-light-activated growth factor receptors, in particular receptor tyrosine kinases were engineered and characterized. Receptor activation with light allows spatio-temporal control compared to ligand-based activation, and especially red light exhibits deeper tissue penetration than other wavelengths of the visible spectrum. Red-light-activated receptor tyrosine kinases robustly activated major growth factor related signaling pathways with a high temporal resolution. Moreover, the remote activation of the proliferative MAPK/Erk pathway by red-light-activated receptor tyrosine kinases in a pancreatic β-cell line was also achieved, through one centimeter thick mouse tissue. Although red-light-activated receptor tyrosine kinases are particularly attractive for applications in animal models due to the deep tissue penetration of red light, a drawback, especially with regard to translation into humans, is the requirement of gene therapy. In a second approach an endogenous light-sensitive mechanism was identified and its potential to promote proliferative and pro-survival signals was explored, towards light-based tissue regeneration without the need for gene transfer. Blue-green light illumination was found to be sufficient for the activation of proliferation and survival promoting signaling pathways in primary pancreatic murine and human islets. Blue-green light also led to an increase in proliferation of primary islet cells, an effect which was shown to be mostly β-cell specific in human islets. Moreover, it was demonstrated that this approach of pancreatic β-cell expansion did not have any negative effect on the β-cell function, in particular on their insulin secretion capacity. In contrast, a trend for enhanced insulin secretion under high glucose conditions after illumination was detected. In order to unravel the detailed characteristics of this endogenous light-sensitive mechanism, the precise light requirements were determined. In addition, the expression of light sensing proteins, OPN3 and rhodopsin, was detected. The observed effects were found to be independent of handling effects such as temperature differences and cytochrome c oxidase dependent ATP increase, but they were found to be enhanced through the knockout of OPN3. The exact mechanism of how islets cells sense light and the identity of the photoreceptor remains unknown. Summarized two new light-based systems with unique features were established that enable the activation of proliferative and pro-survival signaling pathways. While red-light-activated receptor tyrosine kinases open a new avenue for optogenetics research, by allowing non-invasive control of signaling in vivo, the identified endogenous light-sensitive mechanism has the potential to be the basis of a gene therapy-free therapeutical approach for light-based β-cell expansion.

Fluctuations of rectangular young diagrams of interlacing wigner eigenvalues - Erdös, László; Schröder, Dominik J (International Mathematics Research Notices)
We prove a new central limit theorem (CLT) for the difference of linear eigenvalue statistics of a Wigner random matrix H and its minor H and find that the fluctuation is much smaller than the fluctuations of the individual linear statistics, as a consequence of the strong correlation between the eigenvalues of H and H. In particular, our theorem identifies the fluctuation of Kerov's rectangular Young diagrams, defined by the interlacing eigenvalues ofH and H, around their asymptotic shape, the Vershik'Kerov'Logan'Shepp curve. Young diagrams equipped with the Plancherel measure follow the same limiting shape. For this, algebraically motivated, ensemble a CLT has been obtained in Ivanov and Olshanski [20] which is structurally similar to our result but the variance is different, indicating that the analogy between the two models has its limitations. Moreover, our theorem shows that Borodin's result [7] on the convergence of the spectral distribution of Wigner matrices to a Gaussian free field also holds in derivative sense.

An abstraction-refinement methodology for reasoning about network games - Avni, Guy; Guha, Shibashis; Kupferman, Orna (Games)
Network games (NGs) are played on directed graphs and are extensively used in network design and analysis. Search problems for NGs include finding special strategy profiles such as a Nash equilibrium and a globally-optimal solution. The networks modeled by NGs may be huge. In formal verification, abstraction has proven to be an extremely effective technique for reasoning about systems with big and even infinite state spaces. We describe an abstraction-refinement methodology for reasoning about NGs. Our methodology is based on an abstraction function that maps the state space of an NG to a much smaller state space. We search for a global optimum and a Nash equilibrium by reasoning on an under- and an over-approximation defined on top of this smaller state space. When the approximations are too coarse to find such profiles, we refine the abstraction function. We extend the abstraction-refinement methodology to labeled networks, where the objectives of the players are regular languages. Our experimental results demonstrate the effectiveness of the methodology.

Algorithms and conditional lower bounds for planning problems - Chatterjee, Krishnendu; Dvorák, Wolfgang; Henzinger, Monika H; Svozil, Alexander (28th International Conference on Automated Planning and Scheduling)
We consider planning problems for graphs, Markov decision processes (MDPs), and games on graphs. While graphs represent the most basic planning model, MDPs represent interaction with nature and games on graphs represent interaction with an adversarial environment. We consider two planning problems where there are k different target sets, and the problems are as follows: (a) the coverage problem asks whether there is a plan for each individual target set; and (b) the sequential target reachability problem asks whether the targets can be reached in sequence. For the coverage problem, we present a linear-time algorithm for graphs, and quadratic conditional lower bound for MDPs and games on graphs. For the sequential target problem, we present a linear-time algorithm for graphs, a sub-quadratic algorithm for MDPs, and a quadratic conditional lower bound for games on graphs. Our results with conditional lower bounds establish (i) model-separation results showing that for the coverage problem MDPs and games on graphs are harder than graphs and for the sequential reachability problem games on graphs are harder than MDPs and graphs; and (ii) objective-separation results showing that for MDPs the coverage problem is harder than the sequential target problem.

Automated competitive analysis of real time scheduling with graph games - Chatterjee, Krishnendu; Pavlogiannis, Andreas; Kößler, Alexander; Schmid, Ulrich (Real-Time Systems)
This paper is devoted to automatic competitive analysis of real-time scheduling algorithms for firm-deadline tasksets, where only completed tasks con- tribute some utility to the system. Given such a taskset T , the competitive ratio of an on-line scheduling algorithm A for T is the worst-case utility ratio of A over the utility achieved by a clairvoyant algorithm. We leverage the theory of quantitative graph games to address the competitive analysis and competitive synthesis problems. For the competitive analysis case, given any taskset T and any finite-memory on- line scheduling algorithm A , we show that the competitive ratio of A in T can be computed in polynomial time in the size of the state space of A . Our approach is flexible as it also provides ways to model meaningful constraints on the released task sequences that determine the competitive ratio. We provide an experimental study of many well-known on-line scheduling algorithms, which demonstrates the feasibility of our competitive analysis approach that effectively replaces human ingenuity (required Preliminary versions of this paper have appeared in Chatterjee et al. ( 2013 , 2014 ). B Andreas Pavlogiannis pavlogiannis@ist.ac.at Krishnendu Chatterjee krish.chat@ist.ac.at Alexander Kößler koe@ecs.tuwien.ac.at Ulrich Schmid s@ecs.tuwien.ac.at 1 IST Austria (Institute of Science and Technology Austria), Am Campus 1, 3400 Klosterneuburg, Austria 2 Embedded Computing Systems Group, Vienna University of Technology, Treitlstrasse 3, 1040 Vienna, Austria 123 Real-Time Syst for finding worst-case scenarios) by computing power. For the competitive synthesis case, we are just given a taskset T , and the goal is to automatically synthesize an opti- mal on-line scheduling algorithm A , i.e., one that guarantees the largest competitive ratio possible for T . We show how the competitive synthesis problem can be reduced to a two-player graph game with partial information, and establish that the compu- tational complexity of solving this game is Np -complete. The competitive synthesis problem is hence in Np in the size of the state space of the non-deterministic labeled transition system encoding the taskset. Overall, the proposed framework assists in the selection of suitable scheduling algorithms for a given taskset, which is in fact the most common situation in real-time systems design.

Point interactions in systems of fermions - Moser, Thomas
In this thesis we will discuss systems of point interacting fermions, their stability and other spectral properties. Whereas for bosons a point interacting system is always unstable this ques- tion is more subtle for a gas of two species of fermions. In particular the answer depends on the mass ratio between these two species. Most of this work will be focused on the N + M model which consists of two species of fermions with N, M particles respectively which interact via point interactions. We will introduce this model using a formal limit and discuss the N + 1 system in more detail. In particular, we will show that for mass ratios above a critical one, which does not depend on the particle number, the N + 1 system is stable. In the context of this model we will prove rigorous versions of Tan relations which relate various quantities of the point-interacting model. By restricting the N + 1 system to a box we define a finite density model with point in- teractions. In the context of this system we will discuss the energy change when introducing a point-interacting impurity into a system of non-interacting fermions. We will see that this change in energy is bounded independently of the particle number and in particular the bound only depends on the density and the scattering length. As another special case of the N + M model we will show stability of the 2 + 2 model for mass ratios in an interval around one. Further we will investigate a different model of point interactions which was discussed before in the literature and which is, contrary to the N + M model, not given by a limiting procedure but is based on a Dirichlet form. We will show that this system behaves trivially in the thermodynamic limit, i.e. the free energy per particle is the same as the one of the non-interacting system.

PATELLINS are regulators of auxin mediated PIN1 relocation and plant development in Arabidopsis thaliana - Tejos, Ricardo; Rodríguez Furlán, Cecilia; Adamowski, Maciek; Sauer, Michael; Norambuena, Lorena; Friml, Jirí (Journal of Cell Science)
Coordinated cell polarization in developing tissues is a recurrent theme in multicellular organisms. In plants, a directional distribution of the plant hormone auxin is at the core of many developmental programs. A feedback regulation of auxin on the polarized localization of PIN auxin transporters in individual cells has been proposed as a self-organizing mechanism for coordinated tissue polarization, but the molecular mechanisms linking auxin signalling to PIN-dependent auxin transport remain unknown. We performed a microarray-based approach to find regulators of the auxin-induced PIN relocation in the Arabidopsis thaliana root. We identified a subset of a family of phosphatidylinositol transfer proteins (PITP), the PATELLINs (PATL). Here, we show that PATLs are expressed in partially overlapping cells types in different tissues going through mitosis or initiating differentiation programs. PATLs are plasma membrane-associated proteins accumulated in Arabidopsis embryos, primary roots, lateral root primordia, and developing stomata. Higher order patl mutants display reduced PIN1 repolarization in response to auxin, shorter root apical meristem, and drastic defects in embryo and seedling development. This suggests PATLs redundantly play a crucial role in polarity and patterning in Arabidopsis.

Charge sensing and spin relaxation times of holes in Ge hut wires - Vukušić, Lada
A qubit, a unit of quantum information, is essentially any quantum mechanical two-level system which can be coherently controlled. Still, to be used for computation, it has to fulfill criteria. Qubits, regardless of the system in which they are realized, suffer from decoherence. This leads to loss of the information stored in the qubit. The upper bound of the time scale on which decoherence happens is set by the spin relaxation time. In this thesis I studied a two-level system consisting of a Zeeman-split hole spin confined in a quantum dot formed in a Ge hut wire. Such Ge hut wires have emerged as a promising material system for the realization of spin qubits, due to the combination of two significant properties: long spin coherence time as expected for group IV semiconductors due to the low hyperfine interaction and a strong valence band spin-orbit coupling. Here, I present how to fabricate quantum dot devices suitable for electrical transport measurements. Coupled quantum dot devices allowed the realization of a charge sensor, which is electrostatically and tunnel coupled to a quantum dot. By integrating the charge sensor into a radio-frequency reflectometry setup, I performed for the first time single-shot readout measurements of hole spins and extracted the hole spin relaxation times in Ge hut wires.

Synaptotagmins ensure speed and efficiency of inhibitory neurotransmitter release - Chen, Chong
Neuronal networks in the brain consist of two main types of neuron, glutamatergic principal neurons and GABAergic interneurons. Although these interneurons only represent 10–20% of the whole population, they mediate feedback and feedforward inhibition and are involved in the generation of high-frequency network oscillations. A hallmark functional property of GABAergic interneurons, especially of the parvalbumin‑expressing (PV+) subtypes, is the speed of signaling at their output synapse across species and brain regions. Several molecular and subcellular factors may underlie the submillisecond signaling at GABAergic synapses. Such as the selective use of P/Q type Ca2+ channels and the tight coupling between Ca2+ channels and Ca2+ sensors of exocytosis. However, whether the molecular identity of the release sensor contributes to these signaling properties remains unclear. Besides, these interneurons are mainly show depression in response to train of stimuli. How could they keep sufficient release to control the activity of postsynaptic principal neurons during high network activity, is largely elusive. For my Ph.D. work, we firstly examined the Ca2+ sensor of exocytosis at the GABAergic basket cell (BC) to Purkinje cell (PC) synapse in the cerebellum. Immunolabeling suggested that BC terminals selectively expressed synaptotagmin 2 (Syt2), whereas synaptotagmin 1 (Syt1) was enriched in excitatory terminals. Genetic elimination of Syt2 reduced action potential-evoked release to ~10% compared to the wild-type control, identifying Syt2 as the major Ca2+ sensor at BC‑PC synapses. Differential adenovirus-mediated rescue revealed Syt2 triggered release with shorter latency and higher temporal precision, and mediated faster vesicle pool replenishment than Syt1. Furthermore, deletion of Syt2 severely reduced and delayed disynaptic inhibition following parallel fiber stimulation. Thus, the selective use of Syt2 as the release sensor at BC–PC synapse ensures fast feedforward inhibition in cerebellar microcircuits. Additionally, we tested the function of another synaptotagmin member, Syt7, for inhibitory synaptic transmission at the BC–PC synapse. Syt7 is thought to be a Ca2+ sensor that mediates asynchronous transmitter release and facilitation at synapses. However, it is strongly expressed in fast-spiking, PV+ GABAergic interneurons and the output synapses of these neurons produce only minimal asynchronous release and show depression rather than facilitation. How could Syt7, a facilitation sensor, contribute to the depressed inhibitory synaptic transmission needs to be further investigated and understood. Our results indicated that at the BC–PC synapse, Syt7 contributes to asynchronous release, pool replenishment and facilitation. In combination, these three effects ensure efficient transmitter release during high‑frequency activity and guarantee frequency independence of inhibition. Taken together, our results confirmed that Syt2, which has the fastest kinetic properties among all synaptotagmin members, is mainly used by the inhibitory BC‑PC synapse for synaptic transmission, contributing to the speed and temporal precision of transmitter release. Furthermore, we showed that Syt7, another highly expressed synaptotagmin member in the output synapses of cerebellar BCs, is used for ensuring efficient inhibitor synaptic transmission during high activity.

On expansion and topological overlap - Dotterrer, Dominic; Kaufman, Tali; Wagner, Uli (Geometriae Dedicata)
We give a detailed and easily accessible proof of Gromov’s Topological Overlap Theorem. Let X be a finite simplicial complex or, more generally, a finite polyhedral cell complex of dimension d. Informally, the theorem states that if X has sufficiently strong higher-dimensional expansion properties (which generalize edge expansion of graphs and are defined in terms of cellular cochains of X) then X has the following topological overlap property: for every continuous map (Formula presented.) there exists a point (Formula presented.) that is contained in the images of a positive fraction (Formula presented.) of the d-cells of X. More generally, the conclusion holds if (Formula presented.) is replaced by any d-dimensional piecewise-linear manifold M, with a constant (Formula presented.) that depends only on d and on the expansion properties of X, but not on M.

Transition to shocks in TASEP and decoupling of last passage times - Nejjar, Peter (Latin American Journal of Probability and Mathematical Statistics)
We consider the totally asymmetric simple exclusion process in a critical scaling parametrized by a≥0, which creates a shock in the particle density of order aT−1/3, T the observation time. When starting from step initial data, we provide bounds on the limiting law which in particular imply that in the double limit lima→∞limT→∞ one recovers the product limit law and the degeneration of the correlation length observed at shocks of order 1. This result is shown to apply to a general last-passage percolation model. We also obtain bounds on the two-point functions of several airy processes.

Quantum scarred eigenstates in a Rydberg atom chain: Entanglement, breakdown of thermalization, and stability to perturbations - Turner, C J; Michailidis, Alexios; Abanin, D A; Serbyn, Maksym; Papić, Z (Physical Review B)
Recent realization of a kinetically constrained chain of Rydberg atoms by Bernien et al., [Nature (London) 551, 579 (2017)] resulted in the observation of unusual revivals in the many-body quantum dynamics. In our previous work [C. J. Turner et al., Nat. Phys. 14, 745 (2018)], such dynamics was attributed to the existence of “quantum scarred” eigenstates in the many-body spectrum of the experimentally realized model. Here, we present a detailed study of the eigenstate properties of the same model. We find that the majority of the eigenstates exhibit anomalous thermalization: the observable expectation values converge to their Gibbs ensemble values, but parametrically slower compared to the predictions of the eigenstate thermalization hypothesis (ETH). Amidst the thermalizing spectrum, we identify nonergodic eigenstates that strongly violate the ETH, whose number grows polynomially with system size. Previously, the same eigenstates were identified via large overlaps with certain product states, and were used to explain the revivals observed in experiment. Here, we find that these eigenstates, in addition to highly atypical expectation values of local observables, also exhibit subthermal entanglement entropy that scales logarithmically with the system size. Moreover, we identify an additional class of quantum scarred eigenstates, and discuss their manifestations in the dynamics starting from initial product states. We use forward scattering approximation to describe the structure and physical properties of quantum scarred eigenstates. Finally, we discuss the stability of quantum scars to various perturbations. We observe that quantum scars remain robust when the introduced perturbation is compatible with the forward scattering approximation. In contrast, the perturbations which most efficiently destroy quantum scars also lead to the restoration of “canonical” thermalization.

Exceeding the asymptotic limit of polymer drag reduction - Choueiri, George H; Lopez Alonso, Jose M; Hof, Björn (Physical Review Letters)
The drag of turbulent flows can be drastically decreased by adding small amounts of high molecular weight polymers. While drag reduction initially increases with polymer concentration, it eventually saturates to what is known as the maximum drag reduction (MDR) asymptote; this asymptote is generally attributed to the dynamics being reduced to a marginal yet persistent state of subdued turbulent motion. Contrary to this accepted view, we show that, for an appropriate choice of parameters, polymers can reduce the drag beyond the suggested asymptotic limit, eliminating turbulence and giving way to laminar flow. At higher polymer concentrations, however, the laminar state becomes unstable, resulting in a fluctuating flow with the characteristic drag of the MDR asymptote. Our findings indicate that the asymptotic state is hence dynamically disconnected from ordinary turbulence. © 2018 American Physical Society.

Unstable equilibria and invariant manifolds in quasi-two-dimensional Kolmogorov-like flow - Suri, Balachandra; Tithof, Jeffrey; Grigoriev, Roman; Schatz, Michael (Physical Review E)
Recent studies suggest that unstable, nonchaotic solutions of the Navier-Stokes equation may provide deep insights into fluid turbulence. In this article, we present a combined experimental and numerical study exploring the dynamical role of unstable equilibrium solutions and their invariant manifolds in a weakly turbulent, electromagnetically driven, shallow fluid layer. Identifying instants when turbulent evolution slows down, we compute 31 unstable equilibria of a realistic two-dimensional model of the flow. We establish the dynamical relevance of these unstable equilibria by showing that they are closely visited by the turbulent flow. We also establish the dynamical relevance of unstable manifolds by verifying that they are shadowed by turbulent trajectories departing from the neighborhoods of unstable equilibria over large distances in state space.

A homozygous founder mutation in TRAPPC6B associates with a neurodevelopmental disorder characterised by microcephaly epilepsy and autistic features - Marin Valencia, Isaac; Novarino, Gaia; Johansen, Anide; Rosti, Başak; Issa, Mahmoud; Musaev, Damir; Bhat, Gifty; Scott, Eric; Silhavy, Jennifer; Stanley, Valentina; Rosti, Rasim; Gleeson, Jeremy; et al. (Journal of Medical Genetics)
Background: Transport protein particle (TRAPP) is a multisubunit complex that regulates membrane trafficking through the Golgi apparatus. The clinical phenotype associated with mutations in various TRAPP subunits has allowed elucidation of their functions in specific tissues. The role of some subunits in human disease, however, has not been fully established, and their functions remain uncertain. Objective: We aimed to expand the range of neurodevelopmental disorders associated with mutations in TRAPP subunits by exome sequencing of consanguineous families. Methods: Linkage and homozygosity mapping and candidate gene analysis were used to identify homozygous mutations in families. Patient fibroblasts were used to study splicing defect and zebrafish to model the disease. Results: We identified six individuals from three unrelated families with a founder homozygous splice mutation in TRAPPC6B, encoding a core subunit of the complex TRAPP I. Patients manifested a neurodevelopmental disorder characterised by microcephaly, epilepsy and autistic features, and showed splicing defect. Zebrafish trappc6b morphants replicated the human phenotype, displaying decreased head size and neuronal hyperexcitability, leading to a lower seizure threshold. Conclusion: This study provides clinical and functional evidence of the role of TRAPPC6B in brain development and function.

Maps on probability measures preserving certain distances - a survey and some new results - Virosztek, Daniel (Acta Scientiarum Mathematicarum)
Borel probability measures living on metric spaces are fundamental mathematical objects. There are several meaningful distance functions that make the collection of the probability measures living on a certain space a metric space. We are interested in the description of the structure of the isometries of such metric spaces. We overview some of the recent results of the topic and we also provide some new ones concerning the Wasserstein distance. More specifically, we consider the space of all Borel probability measures on the unit sphere of a Euclidean space endowed with the Wasserstein metric W_p for arbitrary p >= 1, and we show that the action of a Wasserstein isometry on the set of Dirac measures is induced by an isometry of the underlying unit sphere.

Statistical mechanics of the uniform electron gas - Lewi, Mathieu; Lieb, Élliott; Seiringer, Robert (Journal de l'Ecole Polytechnique - Mathematiques)
In this paper we define and study the classical Uniform Electron Gas (UEG), a system of infinitely many electrons whose density is constant everywhere in space. The UEG is defined differently from Jellium, which has a positive constant background but no constraint on the density. We prove that the UEG arises in Density Functional Theory in the limit of a slowly varying density, minimizing the indirect Coulomb energy. We also construct the quantum UEG and compare it to the classical UEG at low density.

Agitation modules: Flexible means to accelerate automated freeze substitution - Reipert, Siegfried; Goldammer, Helmuth; Richardson, Christine; Goldberg, Martin; Hawkins, Timothy; Hollergschwandtner, Elena; Kaufmann, Walter; Antreich, Sebastian; Stierhof, York (Journal of Histochemistry and Cytochemistry)
For ultrafast fixation of biological samples to avoid artifacts, high-pressure freezing (HPF) followed by freeze substitution (FS) is preferred over chemical fixation at room temperature. After HPF, samples are maintained at low temperature during dehydration and fixation, while avoiding damaging recrystallization. This is a notoriously slow process. McDonald and Webb demonstrated, in 2011, that sample agitation during FS dramatically reduces the necessary time. Then, in 2015, we (H.G. and S.R.) introduced an agitation module into the cryochamber of an automated FS unit and demonstrated that the preparation of algae could be shortened from days to a couple of hours. We argued that variability in the processing, reproducibility, and safety issues are better addressed using automated FS units. For dissemination, we started low-cost manufacturing of agitation modules for two of the most widely used FS units, the Automatic Freeze Substitution Systems, AFS(1) and AFS2, from Leica Microsystems, using three dimensional (3D)-printing of the major components. To test them, several labs independently used the modules on a wide variety of specimens that had previously been processed by manual agitation, or without agitation. We demonstrate that automated processing with sample agitation saves time, increases flexibility with respect to sample requirements and protocols, and produces data of at least as good quality as other approaches.

Learning equations for extrapolation and control - Sahoo, Subham; Lampert, Christoph; Martius, Georg S (Proceedings of the 35th International Conference on Machine Learning)
We present an approach to identify concise equations from data using a shallow neural network approach. In contrast to ordinary black-box regression, this approach allows understanding functional relations and generalizing them from observed data to unseen parts of the parameter space. We show how to extend the class of learnable equations for a recently proposed equation learning network to include divisions, and we improve the learning and model selection strategy to be useful for challenging real-world data. For systems governed by analytical expressions, our method can in many cases identify the true underlying equation and extrapolate to unseen domains. We demonstrate its effectiveness by experiments on a cart-pendulum system, where only 2 random rollouts are required to learn the forward dynamics and successfully achieve the swing-up task.

Data-dependent stability of stochastic gradient descent - Kuzborskij, Ilja; Lampert, Christoph (Proceedings of the 35 th International Conference on Machine Learning)
We establish a data-dependent notion of algorithmic stability for Stochastic Gradient Descent (SGD), and employ it to develop novel generalization bounds. This is in contrast to previous distribution-free algorithmic stability results for SGD which depend on the worst-case constants. By virtue of the data-dependent argument, our bounds provide new insights into learning with SGD on convex and non-convex problems. In the convex case, we show that the bound on the generalization error depends on the risk at the initialization point. In the non-convex case, we prove that the expected curvature of the objective function around the initialization point has crucial influence on the generalization error. In both cases, our results suggest a simple data-driven strategy to stabilize SGD by pre-screening its initialization. As a corollary, our results allow us to show optimistic generalization bounds that exhibit fast convergence rates for SGD subject to a vanishing empirical risk and low noise of stochastic gradient.

An Austrian proposal for the Classification of Open Access Tuples (COAT) - Distinguish different Open Access types beyond colors - Danowski, Patrick

The convergence of sparsified gradient methods - Alistarh, Dan-Adrian; Hoefler, Torsten; Johansson, Mikael; Konstantinov, Nikola H; Khirirat, Sarit; Renggli, Cedric (Advances in Neural Information Processing Systems 31)
Distributed training of massive machine learning models, in particular deep neural networks, via Stochastic Gradient Descent (SGD) is becoming commonplace. Several families of communication-reduction methods, such as quantization, large-batch methods, and gradient sparsification, have been proposed. To date, gradient sparsification methods--where each node sorts gradients by magnitude, and only communicates a subset of the components, accumulating the rest locally--are known to yield some of the largest practical gains. Such methods can reduce the amount of communication per step by up to three orders of magnitude, while preserving model accuracy. Yet, this family of methods currently has no theoretical justification. This is the question we address in this paper. We prove that, under analytic assumptions, sparsifying gradients by magnitude with local error correction provides convergence guarantees, for both convex and non-convex smooth objectives, for data-parallel SGD. The main insight is that sparsification methods implicitly maintain bounds on the maximum impact of stale updates, thanks to selection by magnitude. Our analysis and empirical validation also reveal that these methods do require analytical conditions to converge well, justifying existing heuristics.

Social network plasticity decreases disease transmission in a eusocial insect - Stroeymeyt, Nathalie; Grasse, Anna V; Crespi, Alessandro; Mersch, Danielle; Cremer, Sylvia; Keller, Laurent (Science)
Animal social networks are shaped by multiple selection pressures, including the need to ensure efficient communication and functioning while simultaneously limiting disease transmission. Social animals could potentially further reduce epidemic risk by altering their social networks in the presence of pathogens, yet there is currently no evidence for such pathogen-triggered responses. We tested this hypothesis experimentally in the ant Lasius niger using a combination of automated tracking, controlled pathogen exposure, transmission quantification, and temporally explicit simulations. Pathogen exposure induced behavioral changes in both exposed ants and their nestmates, which helped contain the disease by reinforcing key transmission-inhibitory properties of the colony's contact network. This suggests that social network plasticity in response to pathogens is an effective strategy for mitigating the effects of disease in social groups.

Nonoptimal gene expression creates latent potential for antibiotic resistance - Palmer, Adam; Chait, Remy P; Kishony, Roy (Molecular Biology and Evolution)
Bacteria regulate genes to survive antibiotic stress, but regulation can be far from perfect. When regulation is not optimal, mutations that change gene expression can contribute to antibiotic resistance. It is not systematically understood to what extent natural gene regulation is or is not optimal for distinct antibiotics, and how changes in expression of specific genes quantitatively affect antibiotic resistance. Here we discover a simple quantitative relation between fitness, gene expression, and antibiotic potency, which rationalizes our observation that a multitude of genes and even innate antibiotic defense mechanisms have expression that is critically nonoptimal under antibiotic treatment. First, we developed a pooled-strain drug-diffusion assay and screened Escherichia coli overexpression and knockout libraries, finding that resistance to a range of 31 antibiotics could result from changing expression of a large and functionally diverse set of genes, in a primarily but not exclusively drug-specific manner. Second, by synthetically controlling the expression of single-drug and multidrug resistance genes, we observed that their fitness-expression functions changed dramatically under antibiotic treatment in accordance with a log-sensitivity relation. Thus, because many genes are nonoptimally expressed under antibiotic treatment, many regulatory mutations can contribute to resistance by altering expression and by activating latent defenses.

Social network plasticity decreases disease transmission in a eusocial insect - Stroeymeyt, Nathalie; Grasse, Anna V; Crespi, Alessandro; Mersch, Danielle; Cremer, Sylvia; Keller, Laurent
Dataset for manuscript 'Social network plasticity decreases disease transmission in a eusocial insect' Compared to previous versions: - raw image files added - correction of URLs within README.txt file

Sensitivity limits of millimeter-wave photonic radiometers based on efficient electro-optic upconverters - Botello, Gabriel; Sedlmeir, Florian; Rueda Sanchez, Alfredo R; Abdalmalak, Kerlos; Brown, Elliott; Leuchs, Gerd; Preu, Sascha; Segovia Vargas, Daniel; Strekalov, Dmitry; Munoz, Luis; Schwefel, Harald (Optica)
Conventional ultra-high sensitivity detectors in the millimeter-wave range are usually cooled as their own thermal noise at room temperature would mask the weak received radiation. The need for cryogenic systems increases the cost and complexity of the instruments, hindering the development of, among others, airborne and space applications. In this work, the nonlinear parametric upconversion of millimeter-wave radiation to the optical domain inside high-quality (Q) lithium niobate whispering-gallery mode (WGM) resonators is proposed for ultra-low noise detection. We experimentally demonstrate coherent upconversion of millimeter-wave signals to a 1550 nm telecom carrier, with a photon conversion efficiency surpassing the state-of-the-art by 2 orders of magnitude. Moreover, a theoretical model shows that the thermal equilibrium of counterpropagating WGMs is broken by overcoupling the millimeter-wave WGM, effectively cooling the upconverted mode and allowing ultra-low noise detection. By theoretically estimating the sensitivity of a correlation radiometer based on the presented scheme, it is found that room-temperature radiometers with better sensitivity than state-of-the-art high-electron-mobility transistor (HEMT)-based radiometers can be designed. This detection paradigm can be used to develop room-temperature instrumentation for radio astronomy, earth observation, planetary missions, and imaging systems.

Contracts for system design - Benveniste, Albert; Nickovic, Dejan; Caillaud, Benoît; Passerone, Roberto; Raclet, Jean Baptiste; Reinkemeier, Philipp; Sangiovanni-Vincentelli, Alberto; Damm, Werner; Henzinger, Thomas A; Larsen, Kim G. (Foundations and Trends in Electronic Design Automation)
Recently, contract-based design has been proposed as an “orthogonal” approach that complements system design methodologies proposed so far to cope with the complexity of system design. Contract-based design provides a rigorous scaffolding for verification, analysis, abstraction/refinement, and even synthesis. A number of results have been obtained in this domain but a unified treatment of the topic that can help put contract-based design in perspective was missing. This monograph intends to provide such a treatment where contracts are precisely defined and characterized so that they can be used in design methodologies with no ambiguity. In particular, this monograph identifies the essence of complex system design using contracts through a mathematical “meta-theory”, where all the properties of the methodology are derived from a very abstract and generic notion of contract. We show that the meta-theory provides deep and illuminating links with existing contract and interface theories, as well as guidelines for designing new theories. Our study encompasses contracts for both software and systems, with emphasis on the latter. We illustrate the use of contracts with two examples: requirement engineering for a parking garage management, and the development of contracts for timing and scheduling in the context of the Autosar methodology in use in the automotive sector.

Coherent-perfect-absorber and laser for bound states in a continuum - Midya, Bikashkali; Konotop, Vladimir (Optics Letters)
It is shown that two fundamentally different phenomena, the bound states in continuum and the spectral singularity (or time-reversed spectral singularity), can occur simultaneously. This can be achieved in a rectangular core dielectric waveguide with an embedded active (or absorbing) layer. In such a system a two-dimensional bound state in a continuum is created in the plane of a waveguide cross section, and it is emitted or absorbed along the waveguide core. The idea can be used for experimental implementation of a laser or a coherent-perfect-absorber for a photonic bound state that resides in a continuous spectrum.

The divergence history of European blue mussel species reconstructed from Approximate Bayesian Computation: The effects of sequencing techniques and sampling strategies - Fraisse, Christelle; Roux, Camille; Gagnaire, Pierre; Romiguier, Jonathan; Faivre, Nicolas; Welch, John; Bierne, Nicolas (PeerJ)
Genome-scale diversity data are increasingly available in a variety of biological systems, and can be used to reconstruct the past evolutionary history of species divergence. However, extracting the full demographic information from these data is not trivial, and requires inferential methods that account for the diversity of coalescent histories throughout the genome. Here, we evaluate the potential and limitations of one such approach. We reexamine a well-known system of mussel sister species, using the joint site frequency spectrum (jSFS) of synonymousmutations computed either fromexome capture or RNA-seq, in an Approximate Bayesian Computation (ABC) framework. We first assess the best sampling strategy (number of: individuals, loci, and bins in the jSFS), and show that model selection is robust to variation in the number of individuals and loci. In contrast, different binning choices when summarizing the jSFS, strongly affect the results: including classes of low and high frequency shared polymorphisms can more effectively reveal recent migration events. We then take advantage of the flexibility of ABC to compare more realistic models of speciation, including variation in migration rates through time (i.e., periodic connectivity) and across genes (i.e., genome-wide heterogeneity in migration rates). We show that these models were consistently selected as the most probable, suggesting that mussels have experienced a complex history of gene flow during divergence and that the species boundary is semi-permeable. Our work provides a comprehensive evaluation of ABC demographic inference in mussels based on the coding jSFS, and supplies guidelines for employing different sequencing techniques and sampling strategies. We emphasize, perhaps surprisingly, that inferences are less limited by the volume of data, than by the way in which they are analyzed.

Can secondary contact following range expansion be distinguished from barriers to gene flow? - Bertl, Johanna; Ringbauer, Harald; Blum, Michaël (PeerJ)
Secondary contact is the reestablishment of gene flow between sister populations that have diverged. For instance, at the end of the Quaternary glaciations in Europe, secondary contact occurred during the northward expansion of the populations which had found refugia in the southern peninsulas. With the advent of multi-locus markers, secondary contact can be investigated using various molecular signatures including gradients of allele frequency, admixture clines, and local increase of genetic differentiation. We use coalescent simulations to investigate if molecular data provide enough information to distinguish between secondary contact following range expansion and an alternative evolutionary scenario consisting of a barrier to gene flow in an isolation-by-distance model. We find that an excess of linkage disequilibrium and of genetic diversity at the suture zone is a unique signature of secondary contact. We also find that the directionality index ψ, which was proposed to study range expansion, is informative to distinguish between the two hypotheses. However, although evidence for secondary contact is usually conveyed by statistics related to admixture coefficients, we find that they can be confounded by isolation-by-distance. We recommend to account for the spatial repartition of individuals when investigating secondary contact in order to better reflect the complex spatio-temporal evolution of populations and species.

Mechanistic framework for cell-intrinsic re-establishment of PIN2 polarity after cell division - Glanc, Matous; Fendrych, Matyas; Friml, Jirí (Nature Plants)
Cell polarity, manifested by the localization of proteins to distinct polar plasma membrane domains, is a key prerequisite of multicellular life. In plants, PIN auxin transporters are prominent polarity markers crucial for a plethora of developmental processes. Cell polarity mechanisms in plants are distinct from other eukaryotes and still largely elusive. In particular, how the cell polarities are propagated and maintained following cell division remains unknown. Plant cytokinesis is orchestrated by the cell plate—a transient centrifugally growing endomembrane compartment ultimately forming the cross wall1. Trafficking of polar membrane proteins is typically redirected to the cell plate, and these will consequently have opposite polarity in at least one of the daughter cells2–5. Here, we provide mechanistic insights into post-cytokinetic re-establishment of cell polarity as manifested by the apical, polar localization of PIN2. We show that the apical domain is defined in a cell-intrinsic manner and that re-establishment of PIN2 localization to this domain requires de novo protein secretion and endocytosis, but not basal-to-apical transcytosis. Furthermore, we identify a PINOID-related kinase WAG1, which phosphorylates PIN2 in vitro6 and is transcriptionally upregulated specifically in dividing cells, as a crucial regulator of post-cytokinetic PIN2 polarity re-establishment.

Language acquisition with communication between learners - Ibsen-Jensen, Rasmus; Tkadlec, Josef; Chatterjee, Krishnendu; Nowak, Martin (Journal of the Royal Society Interface)
We consider a class of students learning a language from a teacher. The situation can be interpreted as a group of child learners receiving input from the linguistic environment. The teacher provides sample sentences. The students try to learn the grammar from the teacher. In addition to just listening to the teacher, the students can also communicate with each other. The students hold hypotheses about the grammar and change them if they receive counter evidence. The process stops when all students have converged to the correct grammar. We study how the time to convergence depends on the structure of the classroom by introducing and evaluating various complexity measures. We find that structured communication between students, although potentially introducing confusion, can greatly reduce some of the complexity measures. Our theory can also be interpreted as applying to the scientific process, where nature is the teacher and the scientists are the students.

Chromatic transitions in the emergence of syntax networks - Corominas-Murtra, Bernat; Fibla, Martí Sànchez; Valverde, Sergi; Solé, Ricard (Royal Society Open Science)
The emergence of syntax during childhood is a remarkable example of how complex correlations unfold in nonlinear ways through development. In particular, rapid transitions seem to occur as children reach the age of two, which seems to separate a two-word, tree-like network of syntactic relations among words from the scale-free graphs associated with the adult, complex grammar. Here, we explore the evolution of syntax networks through language acquisition using the chromatic number, which captures the transition and provides a natural link to standard theories on syntactic structures. The data analysis is compared to a null model of network growth dynamics which is shown to display non-trivial and sensible differences. At a more general level, we observe that the chromatic classes define independent regions of the graph, and thus, can be interpreted as the footprints of incompatibility relations, somewhat as opposed to modularity considerations.

The Dyson equation with linear self-energy: Spectral bands, edges and cusps - Alt, Johannes; Erdös, László; Krüger, Torben H (arXiv)
We study the unique solution $m$ of the Dyson equation \[ -m(z)^{-1} = z - a + S[m(z)] \] on a von Neumann algebra $\mathcal{A}$ with the constraint $Im\,m≥ 0$. Here, $z$ lies in the complex upper half-plane, $a$ is a self-adjoint element of $\mathcal{A}$ and $S$ is a positivity-preserving linear operator on $\mathcal{A}$. We show that $m$ is the Stieltjes transform of a compactly supported $\mathcal{A}$-valued measure on $\mathbb{R}$. Under suitable assumptions, we establish that this measure has a uniformly $1/3$-Hölder continuous density with respect to the Lebesgue measure, which is supported on finitely many intervals, called bands. In fact, the density is analytic inside the bands with a square-root growth at the edges and internal cubic root cusps whenever the gap between two bands vanishes. The shape of these singularities is universal and no other singularity may occur. We give a precise asymptotic description of $m$ near the singular points. These asymptotics generalize the analysis at the regular edges given in the companion paper on the Tracy-Widom universality for the edge eigenvalue statistics for correlated random matrices [arXiv:1804.07744] and they play a key role in the proof of the Pearcey universality at the cusp for Wigner-type matrices [arXiv:1809.03971,arXiv:1811.04055]. We also extend the finite dimensional band mass formula from [arXiv:1804.07744] to the von Neumann algebra setting by showing that the spectral mass of the bands is topologically rigid under deformations and we conclude that these masses are quantized in some important cases.

Convex fair partitions into arbitrary number of pieces - Akopyan, Arseniy; Avvakumov, Sergey; Karasev, Roman
We prove that any convex body in the plane can be partitioned into m convex parts of equal areas and perimeters for any integer m≥2; this result was previously known for prime powers m=pk. We also give a higher-dimensional generalization.

The free boundary Schur process and applications I - Betea, Dan; Bouttier, Jeremie; Nejjar, Peter; Vuletic, Mirjana (Annales Henri Poincare)
We investigate the free boundary Schur process, a variant of the Schur process introduced by Okounkov and Reshetikhin, where we allow the first and the last partitions to be arbitrary (instead of empty in the original setting). The pfaffian Schur process, previously studied by several authors, is recovered when just one of the boundary partitions is left free. We compute the correlation functions of the process in all generality via the free fermion formalism, which we extend with the thorough treatment of “free boundary states.” For the case of one free boundary, our approach yields a new proof that the process is pfaffian. For the case of two free boundaries, we find that the process is not pfaffian, but a closely related process is. We also study three different applications of the Schur process with one free boundary: fluctuations of symmetrized last passage percolation models, limit shapes and processes for symmetric plane partitions and for plane overpartitions.

Graph matching problems for GraphFlow – 6D Large Displacement Scene Flow - Alhaija, Hassan; Sellent, Anita; Kondermann, Daniel; Rother, Carsten
Graph matching problems for large displacement optical flow of RGB-D images.
Keywords: graph matching; quadratic assignment problem<

Emerald Austrian Publications 2013-2017 - Villányi, Márton
Data on Austrian open access publication output at Emerald from 2013-2017 including data analysis.
Keywords: Publication analysis; Bibliography; Open Access

IOP Austrian Publications 2012-2015 - Villányi, Márton
Data on Austrian open access publication output at IOP from 2012-2015 including data analysis.
Keywords: Publication analysis; Bibliography; Open Access

Data Check IOP Scopus vs. Publisher - Villányi, Márton
Comparison of Scopus' and publisher's data on Austrian publication output at IOP.
Keywords: Publication analysis; Bibliography; Open Access

Lizenzverträge mit Open-Access-Komponenten an österreichischen Bibliotheken - Villányi, Márton
Consortial subscription contracts regulate the digital access to publications between publishers and scientific libraries. However, since a couple of years the tendency towards a freely accessible publishing (Open Access) intensifies. As a consequence of this trend the contractual relationship between licensor and licensee is gradually changing as well: More and more contracts exercise influence on open access publishing. The present study attempts to compare Austrian examples of consortial licence contracts, which include components of open access. It describes the difference between pure subscription contracts and differing innovative deals including open access components. Thereby it becomes obvious that for the evaluation of this licence contracts new methods are needed. An essential new element of such analyses is the evaluation of the open access publication numbers. So this study tries to carry out such publication analyses for Austrian open access deals focusing on quantitative questions: How does the number of publications evolve? How does the open access share change? Publications reports of the publishers and database queries from Scopus form the data basis. The analysis of the data points out that differing approaches of contracts result in highly divergent results: Particular deals can prioritize a saving in costs or else the increase of the open access rate. It is to be assumed that within the following years further numerous open access deals will be negotiated. The finding of this study shall provide guidance.

Fluorescence lifetime analysis of FLIM X16 TCSPC data - Hauschild, Robert
Script to perform a simple exponential lifetime fit of a ROI on time stacks acquired with a FLIM X16 TCSPC detector (+example data)
Keywords: FLIM; FRET; fluorescence lifetime imaging

Taylor&Francis Austrian Publications 2013-2017 - Villányi, Márton
Data on Austrian open access publication output at Taylor&Francis from 2013-2017 including data analysis.
Keywords: Publication analysis; Bibliography; Open Access

Springer Austrian Publications 2013-2016 - Villányi, Márton
Data on Austrian open access publication output at Springer from 2013-2016 including data analysis.
Keywords: Publication analysis; Bibliography; Open Access

SAGE Austrian Publications 2013-2017 - Villányi, Márton
Data on Austrian open access publication output at SAGE from 2013-2017 including data analysis.
Keywords: Publication analysis; Bibliography; Open Access

RSC Austrian Publications 2013-2017 - Villányi, Márton
Data on Austrian open access publication output at RSC from 2013-2017 including data analysis.
Keywords: Publication analysis; Bibliography; Open Access

Data Check T&F Scopus vs. FWF - Villányi, Márton
Comparison of Scopus' and FWF's data on Austrian publication output at T&F.
Keywords: Publication analysis; Bibliography; Open Access

Data Check RSC Scopus vs. FWF - Villányi, Márton
Comparison of Scopus' and FWF's data on Austrian publication output at RSC.
Keywords: Publication analysis; Bibliography; Open Access

Nonlinear decoding of a complex movie from the mammalian retina - Botella Soler, Vicent; Deny, Stephane; Martius, Georg S; Marre, Olivier; Tkacik, Gasper (PLoS Computational Biology)
Retina is a paradigmatic system for studying sensory encoding: the transformation of light into spiking activity of ganglion cells. The inverse problem, where stimulus is reconstructed from spikes, has received less attention, especially for complex stimuli that should be reconstructed “pixel-by-pixel”. We recorded around a hundred neurons from a dense patch in a rat retina and decoded movies of multiple small randomly-moving discs. We constructed nonlinear (kernelized and neural network) decoders that improved significantly over linear results. An important contribution to this was the ability of nonlinear decoders to reliably separate between neural responses driven by locally fluctuating light signals, and responses at locally constant light driven by spontaneous-like activity. This improvement crucially depended on the precise, non-Poisson temporal structure of individual spike trains, which originated in the spike-history dependence of neural responses. We propose a general principle by which downstream circuitry could discriminate between spontaneous and stimulus-driven activity based solely on higher-order statistical structure in the incoming spike trains.

Autoregulation of mazEF expression underlies growth heterogeneity in bacterial populations - Nikolic, Nela; Bergmiller, Tobias; Vandervelde, Alexandra; Albanese, Tanino; Gelens, Lendert; Moll, Isabella (Nucleic Acids Research)
The MazF toxin sequence-specifically cleaves single-stranded RNA upon various stressful conditions, and it is activated as a part of the mazEF toxin–antitoxin module in Escherichia coli. Although autoregulation of mazEF expression through the MazE antitoxin-dependent transcriptional repression has been biochemically characterized, less is known about post-transcriptional autoregulation, as well as how both of these autoregulatory features affect growth of single cells during conditions that promote MazF production. Here, we demonstrate post-transcriptional autoregulation of mazF expression dynamics by MazF cleaving its own transcript. Single-cell analyses of bacterial populations during ectopic MazF production indicated that two-level autoregulation of mazEF expression influences cell-to-cell growth rate heterogeneity. The increase in growth rate heterogeneity is governed by the MazE antitoxin, and tuned by the MazF-dependent mazF mRNA cleavage. Also, both autoregulatory features grant rapid exit from the stress caused by mazF overexpression. Time-lapse microscopy revealed that MazF-mediated cleavage of mazF mRNA leads to increased temporal variability in length of individual cells during ectopic mazF overexpression, as explained by a stochastic model indicating that mazEF mRNA cleavage underlies temporal fluctuations in MazF levels during stress.

Evolution of gene dosage on the Z-chromosome of schistosome parasites - Picard, Marion A; Cosseau, Celine; Ferré, Sabrina; Quack, Thomas; Grevelding, Christoph; Couté, Yohann; Vicoso, Beatriz (eLife)
XY systems usually show chromosome-wide compensation of X-linked genes, while in many ZW systems, compensation is restricted to a minority of dosage-sensitive genes. Why such differences arose is still unclear. Here, we combine comparative genomics, transcriptomics and proteomics to obtain a complete overview of the evolution of gene dosage on the Z-chromosome of Schistosoma parasites. We compare the Z-chromosome gene content of African (Schistosoma mansoni and S. haematobium) and Asian (S. japonicum) schistosomes and describe lineage-specific evolutionary strata. We use these to assess gene expression evolution following sex-linkage. The resulting patterns suggest a reduction in expression of Z-linked genes in females, combined with upregulation of the Z in both sexes, in line with the first step of Ohno’s classic model of dosage compensation evolution. Quantitative proteomics suggest that post-transcriptional mechanisms do not play a major role in balancing the expression of Z-linked genes.

Nonlinear decoding of a complex movie from the mammalian retina - Deny, Stephane; Marre, Olivier; Botella-Soler, Vicente; Martius, Georg S; Tkacik, Gasper
This package contains data for the publication "Nonlinear decoding of a complex movie from the mammalian retina" by Deny S. et al, PLOS Comput Biol (2018). The data consists of (i) 91 spike sorted, isolated rat retinal ganglion cells that pass stability and quality criteria, recorded on the multi-electrode array, in response to the presentation of the complex movie with many randomly moving dark discs. The responses are represented as 648000 x 91 binary matrix, where the first index indicates the timebin of duration 12.5 ms, and the second index the neural identity. The matrix entry is 0/1 if the neuron didn't/did spike in the particular time bin. (ii) README file and a graphical illustration of the structure of the experiment, specifying how the 648000 timebins are split into epochs where 1, 2, 4, or 10 discs were displayed, and which stimulus segments are exact repeats or unique ball trajectories. (iii) a 648000 x 400 matrix of luminance traces for each of the 20 x 20 positions ("sites") in the movie frame, with time that is locked to the recorded raster. The luminance traces are produced as described in the manuscript by filtering the raw disc movie with a small gaussian spatial kernel.
Keywords: retina; decoding; regression; neural networks; complex stimulus

Input files and scripts from "Evolution of gene dosage on the Z-chromosome of schistosome parasites" by Picard M.A.L., et al (2018) - Vicoso, Beatriz
Input files and scripts from "Evolution of gene dosage on the Z-chromosome of schistosome parasites" by Picard M.A.L., et al (2018).
Keywords: schistosoma; Z-chromosome; gene expression

Data and Python scripts supporting Python package FAPS - Ellis, Thomas
Data and scripts are provided in support of the manuscript "Efficient inference of paternity and sibship inference given known maternity via hierarchical clustering", and the associated Python package FAPS, available from www.github.com/ellisztamas/faps. Simulation scripts cover: 1. Performance under different mating scenarios. 2. Comparison with Colony2. 3. Effect of changing the number of Monte Carlo draws The final script covers the analysis of half-sib arrays from wild-pollinated seed in an Antirrhinum majus hybrid zone.

Time-lapse microscopy data - Bergmiller, Tobias; Nikolic, Nela
Nela Nikolic, Tobias Bergmiller, Alexandra Vandervelde, Tanino G. Albanese, Lendert Gelens, and Isabella Moll (2018) “Autoregulation of mazEF expression underlies growth heterogeneity in bacterial populations” Nucleic Acids Research, doi: 10.15479/AT:ISTA:74; microscopy experiments by Tobias Bergmiller; image and data analysis by Nela Nikolic.
Keywords: microscopy; microfluidics

Statistical mechanics for metabolic networks during steady state growth - De Martino, Daniele; Mc, Andersson Anna; Bergmiller, Tobias; Guet, Calin C; Tkacik, Gasper (Nature Communications)
Which properties of metabolic networks can be derived solely from stoichiometry? Predictive results have been obtained by flux balance analysis (FBA), by postulating that cells set metabolic fluxes to maximize growth rate. Here we consider a generalization of FBA to single-cell level using maximum entropy modeling, which we extend and test experimentally. Specifically, we define for Escherichia coli metabolism a flux distribution that yields the experimental growth rate: the model, containing FBA as a limit, provides a better match to measured fluxes and it makes a wide range of predictions: on flux variability, regulation, and correlations; on the relative importance of stoichiometry vs. optimization; on scaling relations for growth rate distributions. We validate the latter here with single-cell data at different sub-inhibitory antibiotic concentrations. The model quantifies growth optimization as emerging from the interplay of competitive dynamics in the population and regulation of metabolism at the level of single cells.

Supporting materials "STATISTICAL MECHANICS FOR METABOLIC NETWORKS IN STEADY-STATE GROWTH" - De Martino, Daniele; Tkacik, Gasper
Supporting material to the article STATISTICAL MECHANICS FOR METABOLIC NETWORKS IN STEADY-STATE GROWTH boundscoli.dat Flux Bounds of the E. coli catabolic core model iAF1260 in a glucose limited minimal medium. polcoli.dat Matrix enconding the polytope of the E. coli catabolic core model iAF1260 in a glucose limited minimal medium, obtained from the soichiometric matrix by standard linear algebra (reduced row echelon form). ellis.dat Approximate Lowner-John ellipsoid rounding the polytope of the E. coli catabolic core model iAF1260 in a glucose limited minimal medium obtained with the Lovasz method. point0.dat Center of the approximate Lowner-John ellipsoid rounding the polytope of the E. coli catabolic core model iAF1260 in a glucose limited minimal medium obtained with the Lovasz method. lovasz.cpp This c++ code file receives in input the polytope of the feasible steady states of a metabolic network, (matrix and bounds), and it gives in output an approximate Lowner-John ellipsoid rounding the polytope with the Lovasz method NB inputs are referred by defaults to the catabolic core of the E.Coli network iAF1260. For further details we refer to PLoS ONE 10.4 e0122670 (2015). sampleHRnew.cpp This c++ code file receives in input the polytope of the feasible steady states of a metabolic network, (matrix and bounds), the ellipsoid rounding the polytope, a point inside and it gives in output a max entropy sampling at fixed average growth rate of the steady states by performing an Hit-and-Run Monte Carlo Markov chain. NB inputs are referred by defaults to the catabolic core of the E.Coli network iAF1260. For further details we refer to PLoS ONE 10.4 e0122670 (2015).
Keywords: metabolic networks; e.coli core; maximum entropy; monte carlo markov chain sampling; ellipsoidal rounding

Complex history and differentiation patterns of the t-haplotype, a mouse meiotic driver - Kelemen, Réka K; Vicoso, Beatriz (Genetics)
The t-haplotype, a mouse meiotic driver found on chromosome 17, has been a model for autosomal segregation distortion for close to a century, but several questions remain regarding its biology and evolutionary history. A recently published set of population genomics resources for wild mice includes several individuals heterozygous for the t-haplotype, which we use to characterize this selfish element at the genomic and transcriptomic level. Our results show that large sections of the t-haplotype have been replaced by standard homologous sequences, possibly due to occasional events of recombination, and that this complicates the inference of its history. As expected for a long genomic segment of very low recombination, the t-haplotype carries an excess of fixed nonsynonymous mutations compared to the standard chromosome. This excess is stronger for regions that have not undergone recent recombination, suggesting that occasional gene flow between the t and the standard chromosome may provide a mechanism to regenerate coding sequences that have accumulated deleterious mutations. Finally, we find that t-complex genes with altered expression largely overlap with deleted or amplified regions, and that carrying a t-haplotype alters the testis expression of genes outside of the t-complex, providing new leads into the pathways involved in the biology of this segregation distorter.

Construction of arbitrarily strong amplifiers of natural selection using evolutionary graph theory - Pavlogiannis, Andreas; Tkadlec, Josef; Chatterjee, Krishnendu; Nowak, Martin A. (Communications Biology)
Because of the intrinsic randomness of the evolutionary process, a mutant with a fitness advantage has some chance to be selected but no certainty. Any experiment that searches for advantageous mutants will lose many of them due to random drift. It is therefore of great interest to find population structures that improve the odds of advantageous mutants. Such structures are called amplifiers of natural selection: they increase the probability that advantageous mutants are selected. Arbitrarily strong amplifiers guarantee the selection of advantageous mutants, even for very small fitness advantage. Despite intensive research over the past decade, arbitrarily strong amplifiers have remained rare. Here we show how to construct a large variety of them. Our amplifiers are so simple that they could be useful in biotechnology, when optimizing biological molecules, or as a diagnostic tool, when searching for faster dividing cells or viruses. They could also occur in natural population structures.

Supplementary Files for "Pleiotropy modulates the efficacy of selection in Drosophila melanogaster" - Fraisse, Christelle
File S1. Variant Calling Format file of the ingroup: 197 haploid sequences of D. melanogaster from Zambia (Africa) aligned to the D. melanogaster 5.57 reference genome. File S2. Variant Calling Format file of the outgroup: 1 haploid sequence of D. simulans aligned to the D. melanogaster 5.57 reference genome. File S3. Annotations of each transcript in coding regions with SNPeff: Ps (# of synonymous polymorphic sites); Pn (# of non-synonymous polymorphic sites); Ds (# of synonymous divergent sites); Dn (# of non-synonymous divergent sites); DoS; ⍺ MK . All variants were included. File S4. Annotations of each transcript in non-coding regions with SNPeff: Ps (# of synonymous polymorphic sites); Pu (# of UTR polymorphic sites); Ds (# of synonymous divergent sites); Du (# of UTR divergent sites); DoS; ⍺ MK . All variants were included. File S5. Annotations of each transcript in coding regions with SNPGenie: Ps (# of synonymous polymorphic sites); πs (synonymous diversity); Ss_p (total # of synonymous sites in the polymorphism data); Pn (# of non-synonymous polymorphic sites); πn (non-synonymous diversity); Sn_p (total # of non-synonymous sites in the polymorphism data); Ds (# of synonymous divergent sites); ks (synonymous evolutionary rate); Ss_d (total # of synonymous sites in the divergence data); Dn (# of non-synonymous divergent sites); kn (non-synonymous evolutionary rate); Sn_d (total # of non- synonymous sites in the divergence data); DoS; ⍺ MK . All variants were included. File S6. Gene expression values (RPKM summed over all transcripts) for each sample. Values were quantile-normalized across all samples. File S7. Final dataset with all covariates, ⍺ MK , ωA MK and DoS for coding sites, excluding variants below 5% frequency. File S8. Final dataset with all covariates, ⍺ MK , ωA MK and DoS for non-coding sites, excluding variants below 5% frequency. File S9. Final dataset with all covariates, ⍺ EWK , ωA EWK and deleterious SFS for coding sites obtained with the Eyre-Walker and Keightley method on binned data and using all variants.
Keywords: (mal)adaptation; pleiotropy; selective constraint; evo-devo; gene expression; Drosophila melanogaster

Dyson equation and eigenvalue statistics of random matrices - Alt, Johannes
The eigenvalue density of many large random matrices is well approximated by a deterministic measure, the self-consistent density of states. In the present work, we show this behaviour for several classes of random matrices. In fact, we establish that, in each of these classes, the self-consistent density of states approximates the eigenvalue density of the random matrix on all scales slightly above the typical eigenvalue spacing. For large classes of random matrices, the self-consistent density of states exhibits several universal features. We prove that, under suitable assumptions, random Gram matrices and Hermitian random matrices with decaying correlations have a 1/3-Hölder continuous self-consistent density of states ρ on R, which is analytic, where it is positive, and has either a square root edge or a cubic root cusp, where it vanishes. We, thus, extend the validity of the corresponding result for Wigner-type matrices from [4, 5, 7]. We show that ρ is determined as the inverse Stieltjes transform of the normalized trace of the unique solution m(z) to the Dyson equation −m(z) −1 = z − a + S[m(z)] on C N×N with the constraint Im m(z) ≥ 0. Here, z lies in the complex upper half-plane, a is a self-adjoint element of C N×N and S is a positivity-preserving operator on C N×N encoding the first two moments of the random matrix. In order to analyze a possible limit of ρ for N → ∞ and address some applications in free probability theory, we also consider the Dyson equation on infinite dimensional von Neumann algebras. We present two applications to random matrices. We first establish that, under certain assumptions, large random matrices with independent entries have a rotationally symmetric self-consistent density of states which is supported on a centered disk in C. Moreover, it is infinitely often differentiable apart from a jump on the boundary of this disk. Second, we show edge universality at all regular (not necessarily extreme) spectral edges for Hermitian random matrices with decaying correlations.